Polyester film and method for manufacturing the same

CN122996111APending Publication Date: 2026-10-27MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202580023004.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-25
Filing Date
2025-03-24
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0046]根据本发明,能够提供一种电池外包装用聚酯膜,其能够防止与金属箔等其他构件的密合性降低,并且在层压加工时容易层叠在其他膜上等。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

A polyester film containing polybutylene terephthalate and polyethylene terephthalate, the heat shrinkage of the polyester film in one of the longitudinal and transverse directions being less than 5% and the heat shrinkage in the other direction being greater than 2.5% after heat treatment at 160°C for 15 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polyester film for battery packaging, a method for manufacturing the same, a laminate containing the polyester film for battery packaging, and battery packaging materials. Background Technology

[0002] Previously, polyester films, especially polyethylene terephthalate films and polyethylene naphthalate films, have excellent mechanical properties, heat resistance, and chemical resistance, and have been used for various applications such as packaging, electronic components, electrical insulation, metal lamination, optical applications such as components for foldable displays, flexible displays, and rollable displays, touch panels, anti-reflection, and preventing glass scattering (for example, see Patent Documents 1 and 2).

[0003] In many of these applications, the polyester film is not used directly as a single unit, but rather formed and processed for use. In these cases, many products also prioritize mechanical properties. Therefore, polyester film alone cannot meet the required quality, and many products are composited with other layers (such as resin layers, metal layers, etc.).

[0004] For example, in lithium-ion batteries, outer packaging materials are used to seal the electrodes, electrolyte, and other components. Historically, metal materials were commonly used for this purpose.

[0005] On the other hand, in recent years, with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, and mobile phones, there is a growing demand for lithium-ion batteries in various shapes, as well as thinner and lighter designs. However, the metal packaging materials that have been commonly used in the past have limitations in keeping up with the diversification of shapes and in achieving lightweight designs.

[0006] Therefore, in recent years, as an outer packaging material that is easy to process into various shapes and can achieve thinness and lightness, bags (soft packs) made of laminated plastic films formed by pressing plastic films onto metal foils such as aluminum foil have begun to be used. In bag-shaped outer packaging materials, recesses are usually formed by cold forming the laminate, and energy storage devices such as electrodes and electrolytes are placed in the space formed by the recesses. By thermally fusing the laminates together, a lithium-ion battery or the like is obtained, which houses the energy storage devices inside the outer packaging material.

[0007] Polyamide is widely used as the substrate for the aforementioned laminates from the viewpoint of excellent formability. In addition to formability, moisture resistance, sealing, and chemical resistance are sometimes required, and structures consisting of polyester film / polyamide film / metal foil / sealing film in sequence from the outermost layer have been studied.

[0008] Furthermore, in order to efficiently integrate lithium-ion batteries with printed circuit boards and other components within electronic devices that require miniaturization and thinning in recent years, research is underway to make the corners of pouch cells into sharp shapes. Moreover, from the perspective of further increasing battery capacity and energy density per unit volume by increasing the content of each pouch cell, there is increasing emphasis in recent years on developing pouch cell films with excellent formability that can form deeper recesses in cold forming processes such as deep drawing. Therefore, for example, Patent Documents 1 and 2 have investigated the use of polyester films with polybutylene terephthalate (PET) as the main component, which has good formability, as battery packaging materials. Furthermore, Patent Documents 5-7 have also investigated the use of polyester films containing PET as battery packaging materials.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent Application Publication No. 2006-341546

[0012] Patent Document 2: Japanese Patent Application Publication No. 2004-122767

[0013] Patent Document 3: Japanese Patent Application Publication No. 2012-077292

[0014] Patent Document 4: WO2014 / 017457

[0015] Patent Document 5: Japanese Patent Application Publication No. 2017-177412

[0016] Patent Document 6: Japanese Patent Application Publication No. 2022-056851

[0017] Patent Document 7: WO2017 / 057773 Summary of the Invention

[0018] The problem that the invention aims to solve

[0019] However, the polyester films described in Patent Documents 1 and 2 are not intended for use as battery packaging. The polyester films disclosed in Patent Documents 3, 4, and 6, which are primarily composed of polybutylene terephthalate (PBT), suffer from high heat shrinkage due to PBT's high crystallinity and low melting point. High heat shrinkage can cause difficulties in laminating other films, for example, during lamination processes. Therefore, while reducing PBT could be considered, reducing the amount of PBT would result in an excessively low heat shrinkage rate and reduced adhesion to other components such as metal foils. Furthermore, the polybutylene terephthalate disclosed in Patent Document 5 is a polyester-based elastomer, which may also have a high heat shrinkage rate. Moreover, even Patent Document 7 presents the possibility that the heat shrinkage rate cannot be properly controlled or the mechanical strength cannot be sufficiently improved.

[0020] Therefore, the present invention addresses the problem of providing a polyester film for battery packaging that prevents a decrease in adhesion to other components such as metal foil and is easy to laminate onto other films during lamination.

[0021] Solution for solving the problem

[0022] Through in-depth research, the inventors discovered that by including polyethylene terephthalate and polybutylene terephthalate in the polyester film, and subjecting it to heat treatment at 160°C for 15 minutes, the thermal shrinkage rate in one of the longitudinal and transverse directions is less than a specified value, while the thermal shrinkage rate in the other direction is higher than a specified value, thus solving the above-mentioned problems and completing the following invention.

[0023] That is, the present invention provides the following [1] to

[21] .

[0024] [1] A polyester film for battery packaging, the polyester film for battery packaging contains polybutylene terephthalate and polyethylene terephthalate, and after heat treatment at 160°C for 15 minutes, the thermal shrinkage rate of the polyester film in one direction (longitudinal and transverse) is less than 5% and the thermal shrinkage rate in the other direction is greater than 2.5%.

[0025] [2] The polyester film for battery packaging described in [1] above, wherein the endothermic peak at the time of temperature rise is obtained by differential scanning calorimetry.

[0026] [3] The polyester film for battery packaging as described in [1] or [2] above, wherein the ratio of the longitudinal heat shrinkage rate to the transverse heat shrinkage rate (MD / TD) is 0.7 or more and 2 or less.

[0027] [4] The polyester film for battery packaging according to any one of [1] to [3] above, wherein the ratio of polyethylene terephthalate to polybutylene terephthalate (PET / PBT) is 55 / 45 or more and 95 / 5 or less by mass.

[0028] [5] The polyester film for battery outer packaging according to any one of [1] to [4] above, wherein the puncture strength is 480 N / mm or more.

[0029] [6] The polyester film for battery outer packaging according to any one of [1] to [5] above, wherein the displacement during puncture is 4 mm or more.

[0030] [7] The polyester film for battery outer packaging according to any one of [1] to [6] above, wherein the puncture strength is not all less than 0.036.

[0031] [8] The polyester film for battery outer packaging according to any one of [1] to [7] above, wherein the displacement during puncture is not less than 0.034.

[0032] [9] The polyester film for battery outer packaging according to any one of [1] to [8] above, wherein the haze is 10% or less.

[0033]

[10] The polyester film for battery outer packaging according to any one of [1] to [9] above, wherein the melting point of the first temperature scan is above 230°C.

[0034]

[11] The polyester film for battery outer packaging according to any one of [1] to

[10] above, wherein the intrinsic viscosity of the polyester film is 0.6 dL / g or more and 0.85 dL / g or less.

[0035]

[12] The polyester film for battery packaging according to any one of [1] to

[11] above, wherein the polyester film for battery packaging is a biaxially stretched polyester film.

[0036]

[13] A polyester film for battery packaging, wherein the polyester film for battery packaging is manufactured according to the manufacturing method of the polyester film for battery packaging according to any one of [1] to

[12] above, comprising a stretching process in the longitudinal and transverse directions, wherein the preheating temperature during transverse stretching is 60°C or higher and 90°C or lower, and the stretching temperature is 70°C or higher and 120°C or lower.

[0037]

[14] In the method for manufacturing the polyester film for battery outer packaging described in

[13] above, the heat setting temperature after stretching is above 190°C.

[0038]

[15] In the method for manufacturing a polyester film for battery packaging as described in

[13] or

[14] above, the ratio of transverse stretch ratio to longitudinal stretch ratio (TD / MD) is 1 or more and 1.7 or less.

[0039]

[16] The method for manufacturing a polyester film for battery outer packaging according to any one of

[13] to

[15] above, wherein the stretching temperature during longitudinal stretching is 50°C or higher and 85°C or lower.

[0040]

[17] The method for manufacturing a polyester film for battery outer packaging according to any one of

[13] to

[16] above, wherein the longitudinal stretch ratio is 2.5 times or more and 4.5 times or less.

[0041]

[18] The method for manufacturing a polyester film for battery outer packaging according to any one of

[13] to

[17] above, wherein the transverse stretch ratio is 3.5 times or more and 6 times or less.

[0042]

[19] A laminate comprising a polyester film for battery packaging according to any one of [1] to

[12] above, and at least one of a resin layer or a metal layer.

[0043]

[20] A battery outer packaging material comprising a polyester film according to any one of [1] to

[12] above or a laminate according to

[19] above.

[0044]

[21] A battery having the battery outer packaging material according to

[20] above.

[0045] Invention Effects

[0046] According to the present invention, a polyester film for battery packaging can be provided, which can prevent the decrease in adhesion to other components such as metal foil, and can be easily laminated onto other films during lamination. Detailed Implementation

[0047] [Polyester film for battery packaging]

[0048] The polyester film for battery packaging of the present invention (hereinafter sometimes referred to as "this polyester film") contains polybutylene terephthalate (hereinafter sometimes referred to as "PBT") and polyethylene terephthalate (hereinafter sometimes referred to as "PET").

[0049] (PBT)

[0050] The PBT constituting this polyester film is a condensation polymer of dicarboxylic acid and diol components. It is a polyester containing terephthalic acid as the dicarboxylic acid component and 1,4-butanediol as the diol component. PBT has terephthalic acid and 1,4-butanediol as the main components. PBT preferably contains more than 50 mol% terephthalic acid as the dicarboxylic acid component and more than 50 mol% 1,4-butanediol (BDO) as the diol component.

[0051] The proportion of terephthalic acid in the dicarboxylic acid component of PBT is more preferably 70 mol% or more, further preferably 90 mol% or more, and most preferably 100 mol%. Furthermore, the proportion of 1,4-butanediol in the diol component of PBT is more preferably 70 mol% or more, further preferably 90 mol% or more, and most preferably 100 mol%. Therefore, homopolymer PBT is the most preferred PBT.

[0052] Regarding PBT, by increasing the ratio of terephthalic acid and BDO, as described later, it is easy to achieve a thermal shrinkage rate in the other direction that exceeds the specified value. Furthermore, it is easier to utilize the physical properties of PBT, resulting in good elongation and other desirable characteristics.

[0053] In PBT, there are no particular restrictions on dicarboxylic acids other than terephthalic acid. Examples include: aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-benzophenone dicarboxylic acid, 4,4'-diphenoxyethane dicarboxylic acid, 4,4'-diphenyl sulfone dicarboxylic acid, and 2,6-naphthalene dicarboxylic acid; alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, and sebacic acid. Only one of these dicarboxylic acids (excluding terephthalic acid) can be used, or two or more can be used in combination.

[0054] In this invention, there are no particular limitations on diol components other than BDO. Examples include: aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,5-pentanediol, neopentanediol, 1,6-hexanediol, 1,8-octanediol, and dibutylene glycol; alicyclic diols such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,1-cyclohexanediethanol, and 1,4-cyclohexanediethanol; and aromatic diols such as benzenediethanol, 4,4'-dihydroxybiphenyl, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.

[0055] These diol components, excluding BDO, can be used individually or in combination with two or more.

[0056] In addition, PBT can also use one or more of the following as copolymerizing components: hydroxycarboxylic acids such as lactic acid, glycolic acid, m-hydroxybenzoic acid, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and p-β-hydroxyethoxybenzoic acid; alkoxycarboxylic acids; monofunctional components such as stearyl alcohol, benzyl alcohol, stearic acid, benzoic acid, tert-butylbenzoic acid, and benzoylbenzoic acid; and polyfunctional components with trifunctional or higher functions such as tricarboxylic acid, trimellitic acid, pyromellitic acid, pyromellitic acid, gallic acid, trimethylolethane, trimethylolpropane, glycerol, and pentaerythritol.

[0057] The intrinsic viscosity of PBT is not particularly limited, but is preferably 0.7 dL / g or higher and 1.4 dL / g or lower, more preferably 0.73 dL / g or higher and 1.37 dL / g or lower, even more preferably 0.77 dL / g or higher and 1.33 dL / g or lower, and even more preferably 0.8 dL / g or higher and 1.3 dL / g or lower. Controlling the intrinsic viscosity of PBT within the above range facilitates good heat resistance, productivity, and moldability of the polyester film. It should be noted that the intrinsic viscosity of PBT can be appropriately set within the above range and is not limited to the following values; for example, it can also be 0.8 dL / g or higher and 1.2 dL / g or lower, 0.8 dL / g or higher and 1.1 dL / g, 0.8 dL / g or higher and 1 dL / g or lower, etc.

[0058] It should be noted that when using two or more types of PBTs with different intrinsic viscosities, the intrinsic viscosity refers to the intrinsic viscosity of these blended polyesters. Furthermore, intrinsic viscosity can be measured using conventional methods, such as an Ubbelohde viscometer with phenol:tetrachloroethane = 1:1 as the solvent at 30°C.

[0059] (PET)

[0060] The PET that constitutes this film is a condensation polymer of dicarboxylic acid and glycol components, and is a polyester containing terephthalic acid as the dicarboxylic acid component and ethylene glycol as the glycol component. PET has terephthalic acid and ethylene glycol as the main components, and preferably contains more than 50 mol% terephthalic acid as the dicarboxylic acid component and more than 50 mol% ethylene glycol as the glycol component.

[0061] The proportion of terephthalic acid in the dicarboxylic acid component of PET is more preferably 70 mol% or more, further preferably 90 mol% or more, and most preferably 100 mol%. Furthermore, the proportion of ethylene glycol in the glycol component is more preferably 70 mol% or more, further preferably 90 mol% or more, and most preferably 100 mol%. Therefore, homopolymer PET is the most preferred PET.

[0062] In the case of PET, by increasing the ratio of terephthalic acid and ethylene glycol, it is easier to utilize the physical properties of PET and reduce the heat shrinkage rate. Furthermore, it is easier to impart a certain level of mechanical strength and improve puncture resistance. This also makes it easier to increase martensitic hardness, indentation hardness, and elastic deformation power.

[0063] In PET, there are no particular restrictions on dicarboxylic acids other than terephthalic acid. Examples of dicarboxylic acids other than terephthalic acid include those listed above in PBT. In PET, only one dicarboxylic acid other than terephthalic acid may be used, or two or more may be used in combination. Furthermore, there are no particular restrictions on diols other than ethylene glycol. Specific examples include 1,4-butanediol and other diols other than ethylene glycol listed in the PBT examples above.

[0064] Furthermore, in PET, one or more of the following can be used as copolymer components: hydroxycarboxylic acid, monofunctional components, and polyfunctional components with three or more functions, as specifically described in PBT.

[0065] The intrinsic viscosity of PET is not particularly limited, but is preferably 0.5 dL / g or higher and 1 dL / g or lower, more preferably 0.53 dL / g or higher and 0.96 dL / g or lower, even more preferably 0.57 dL / g or higher and 0.93 dL / g or lower, and even more preferably 0.6 dL / g or higher and 0.9 dL / g or lower. Controlling the intrinsic viscosity of PET within the above range facilitates good heat resistance, productivity, and moldability of the polyester film. It should be noted that the intrinsic viscosity of PET can be appropriately set within the above range and is not limited to the following values; for example, it can also be 0.6 dL / g or higher and 0.8 dL / g or 0.6 dL / g or higher and 0.75 dL / g or lower.

[0066] (PBT to PET mass ratio)

[0067] In this polyester film, the content ratio of polyethylene terephthalate to polybutylene terephthalate (PET / PBT) is preferably 55 / 45 or more and 95 / 5 or less by mass. By maintaining this mass ratio of 55 / 45 or more, the heat resistance of the polyester film can be improved, and the heat shrinkage rate can be prevented from exceeding the desired level. Furthermore, the mechanical strength of the film is improved, and puncture resistance and other properties are also readily improved. Moreover, film formation by sequential biaxial stretching becomes easier, and the heat setting temperature after stretching can be increased more easily.

[0068] Furthermore, by setting it to 95 / 5 or less, as described later, it is easy to make the thermal shrinkage rate in the other direction exceed the specified value. Additionally, it is easier to ensure elongation and also easier to increase the displacement during puncture, as described later.

[0069] The aforementioned mass ratio is more preferably 60 / 40 or more, further preferably 63 / 37 or more, even more preferably 65 / 35 or more, particularly preferably 72 / 28 or more; further preferably 90 / 10 or less, even more preferably 85 / 15 or less, and even more preferably 82 / 18 or less.

[0070] This polyester film may contain resins other than PET and PBT as described above, without impairing the effects of the present invention. Examples of resins other than PET and PBT include: polyester resins other than PET and PBT, and resins other than polyester resins. Resins other than polyester resins include: polystyrene resins, polyvinyl chloride resins, polyvinylidene chloride resins, chlorinated polyethylene resins, polycarbonate resins, polyamide resins, polyacetal resins, acrylic resins, ethylene-vinyl acetate copolymers, polymethylpentene resins, polyvinyl alcohol resins, cyclic olefin resins, polylactic acid resins, polybutylene succinate resins, polyacrylonitrile resins, polyethylene oxide resins, cellulose resins, polyimide resins, polyurethane resins, polyphenylene sulfide resins, polyphenylene ether resins, polyvinyl alcohol acetal resins, polybutadiene resins, polybutene resins, polyamide-imide resins, polyamide-bismaleimide resins, polyetherimide resins, polyetheretherketone resins, polyetherketone resins, polyethersulfone resins, polyketone resins, polysulfone resins, aramid resins, and fluorine resins, etc.

[0071] In this polyester film, PBT and PET are preferably the main components. Specifically, the combined amount of PBT and PET, based on the total amount of the polyester film, is preferably 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. Furthermore, there is no particular upper limit to the combined content of PBT and PET, as long as it is 100% by mass or less. However, from the viewpoint of compounding additives, it is preferable to be less than 100% by mass based on the total amount of the polyester film.

[0072] The thickness of this polyester film is not particularly limited as long as it falls within the range suitable for molding, for example, it is 6 μm or more and 90 μm or less, preferably 8 μm or more and 70 μm or less, more preferably 9 μm or more and 50 μm or less, and even more preferably 10 μm or more and 40 μm or less. By keeping the film thickness within the specified range, the heat shrinkage rate is prevented from exceeding the desired value, and the heat shrinkage rate in both the longitudinal and width directions is easily controlled.

[0073] This polyester film is preferably a biaxially stretched polyester film. By using a biaxially stretched polyester film, the heat shrinkage rate in both the longitudinal and width directions can be easily controlled.

[0074] This polyester film can be a single-layer structure (single-layer film) or a multi-layer structure with two or more layers (multi-layer film). In the case of a multi-layer structure, it is preferable to have a surface layer and a core layer. It should be noted that the surface layer is the layer that constitutes one surface of this polyester film, and the core layer is the layer disposed inside the surface layer. In addition to the surface layer and core layer constituting one surface, this polyester film may also have a surface layer constituting another surface of this polyester film.

[0075] In the case of a multilayer structure, this polyester film can be a two-layer structure of surface layer / core layer, a three-layer structure of surface layer / core layer / surface layer, or a multilayer structure with four or more layers, but a three-layer structure of surface layer / core layer / surface layer is preferred. In multilayer structures with four or more layers, it is preferable to have two or more core layers.

[0076] In the case of a multilayer structure, it is preferable that each layer contains both PET and PBT, and the ratio of PET to PBT content in each layer is preferably as described above. Alternatively, the ratio of PET to PBT content in a portion of each layer may be as described above, or the ratio may be as described above in all layers of each layer. Furthermore, the ratio of PET to PBT content in the entire multilayer structure is preferably as described above. Moreover, each layer may contain resins other than PET and PBT, as described above, and the total content of PET and PBT in each layer may be calculated based on each layer as described above, rather than based on the total amount of the polyester film.

[0077] As described later, for example, the core layer may contain PET and PBT, while the surface layer may contain PET but not PBT.

[0078] Furthermore, in the case of a multilayer structure, the material composition (e.g., resin composition) constituting a surface layer can differ from the material composition constituting at least one other layer. For example, the material composition constituting the surface layer can differ from the material composition constituting the core layer. Specifically, the content of PET and PBT in each layer can be adjusted so that the content at the film surface and at the center in the film thickness direction is as shown in a preferred embodiment described later.

[0079] Furthermore, for example, it is preferred that the PET content in at least one surface layer is greater than the PBT content in at least one of the other layers, based on the proportion, wherein, it is preferred that the PET content in at least one surface layer (hereinafter referred to as content (A1)) is greater than the PET content (A2) in the core layer.

[0080] It should be noted that "different material composition" means that the material composition is not the same or substantially different. "Substantially different" means that, when comparing the various components that make up each material, the content difference of each component exceeds ±1% by mass, or / and when containing mutually different components, the total content of the different components relative to the total material is more than 2% by mass.

[0081] It is preferable that the thickness of the surface layer is less than that of the core layer. The thickness of each surface layer is preferably 1% to 20% of the overall thickness of the polyester film, more preferably 2% to 15%, and even more preferably 4% to 12%. When the thickness of the surface layer is controlled within such a range, if the surface layer contains particles as described later, the particles can impart slipperiness without compromising transparency, and problems such as particle shedding are less likely to occur.

[0082] Furthermore, from the same point of view, the thickness of each surface layer is preferably 0.2 μm or more and 10 μm or less, more preferably 0.4 μm or more and 7.5 μm or less, even more preferably 0.8 μm or more and 6 μm or less, and even more preferably 1 μm or more and 4 μm or less.

[0083] The core layer is preferably a layer that forms the central portion in the thickness direction of the polyester film. The thickness of the core layer is preferably 65% ​​or more and 98% or less of the overall thickness of the polyester film, more preferably 70% or more and 96% or less, and even more preferably 75% or more and 94% or less.

[0084] Furthermore, the thickness of the core layer is preferably 7 μm or more and 88 μm or less, more preferably 10 μm or more and 70 μm or less, and even more preferably 15 μm or more and 55 μm or less.

[0085] Furthermore, the thickness ratio of each surface layer to the core layer is, for example, 1 / 99 or more and 40 / 60 or less, preferably 2 / 98 or more and 35 / 65 or less, more preferably 4 / 96 or more and 30 / 70 or less, and even more preferably 6 / 94 or more and 25 / 75 or less.

[0086] Furthermore, when the polyester film has a three-layer structure of surface layer, core layer, and surface layer, the thickness ratio (surface layer thickness: core layer thickness: surface layer thickness) is preferably 1-20:65-98:1-20, more preferably 2-15:70-96:2-15, and even more preferably 3-12.5:75-94:3-12.5.

[0087] The core layer thickness mentioned here refers to the total thickness of the core layers when there are two or more core layers.

[0088] [The content of each resin on the membrane surface and in the central part]

[0089] Hereinafter, a preferred embodiment of the resin content of each resin on the film surface and in the central portion will be described. In a preferred embodiment, the PET content (hereinafter also referred to as "content (A1)") of at least one surface of the polyester film, on a mass ratio basis, is greater than the PET content (hereinafter also referred to as "content (A2)") in the central portion of the film thickness direction. When the polyester film contains both PBT and PET, and the PET content (A1) on the surface is increased, the puncture strength, martensitic hardness, indentation hardness, etc., are improved, the pinhole resistance is excellent, and it is not easy to break when external force is applied. When used as a battery outer packaging material, it is not easily damaged even if the battery is damaged in an accident. In addition, due to the high martensitic hardness and indentation hardness, it is not easy for the battery to expand even when heated, and for example, it can prevent contact with the battery casing further out of the battery outer packaging material.

[0090] Furthermore, when this polyester film contains both PBT and PET, and the PET content (A1) on the surface is greater than the content (A2), the elastic deformation power can be improved. A high elastic deformation power means that even if the molded article is deformed, its shape can easily return to its original state. Therefore, the shape of the molded article is easily maintained during molding, resulting in molded articles with excellent design and shape recovery, and less likelihood of molding defects. In addition, even when subjected to external forces such as punctures, it can easily return to its original shape after the external force is removed, and deformation of the molded article can be more effectively suppressed.

[0091] This polyester film only requires that the PET content (A1) on one surface is greater than the content (A2) in the center of the film, but it is preferable that the PET content (A1) on both surfaces is greater than the content (A2).

[0092] In a preferred embodiment, the PET content (A1) of at least one surface of the polyester film is, for example, 70% by mass or more, preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 89% by mass or more, and even more preferably 92% by mass or more. Furthermore, the PET content (A1) only needs to be 100% by mass or less; for example, if PBT is present on one surface, it is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less. It should be noted that as long as the PET content (A1) of the surface with a content greater than that of the content (A2) is above the lower limit and below the upper limit, it is acceptable, but it is preferable that the PET content (A1) of both surfaces is above the lower limit and below the upper limit.

[0093] Furthermore, in a preferred embodiment, the PET content (A2) in the central portion of the polyester film in the film thickness direction is, for example, only 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, further preferably 63% by mass or more, even more preferably 65% ​​by mass or more, particularly preferably 72% by mass or more; furthermore, it is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and even more preferably 82% by mass or less.

[0094] In a preferred embodiment, the PET content (A1) of at least one surface is greater than the PET content (A2) of the central portion, but the difference between the contents (A1) and (A2) (A1-A2) is preferably within a specific range, specifically preferably 3% by mass or more and 35% by mass or less. By controlling this content difference within a specific range, the polyester film exhibits good mechanical strength, making it easier to further improve puncture resistance, martensitic hardness, indentation hardness, and elastic deformation power. The content difference (A1-A2) is more preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more; furthermore, it is more preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 22% by mass or less.

[0095] In a preferred embodiment, the ratio (B1 / A1) of the PBT content (B1) to the PET content (A1) on at least one surface of the polyester film is preferably 20 / 80 or less by mass, more preferably 15 / 85 or less, further preferably 10 / 90 or less, and even more preferably 8 / 92 or less. By setting the content ratio (B1 / A1) to the aforementioned value or less, it is easy to improve the martensitic hardness, indentation hardness, elastic deformation power, etc.

[0096] The polyester film may be free of PBT on at least one surface, so the content ratio (B1 / A1) only needs to be 0 / 100 or more. However, the polyester film may also contain PBT on at least one surface, in which case the above-mentioned content ratio (B1 / A1) is preferably 1 / 99 or more by mass, more preferably 2 / 98 or more, and even more preferably 3 / 97 or more.

[0097] It should be noted that the content ratio (B1 / A1) is only required to be below or above the above-mentioned upper limit value on the surface where the content (A1) is greater than the content (A2), but it is preferable that the content ratio (B1 / A1) of the two surfaces is below or above the above-mentioned upper limit value.

[0098] In a preferred embodiment, the ratio (B2 / A2) of PBT content (B2) to PET content (A2) at the center of the polyester film in the film thickness direction is preferably 5 / 95 or more and 45 / 55 or less by mass. By setting the above mass ratio to 45 / 55 or less, the mechanical strength of the polyester film can be improved, easily enhancing resistance to pinholes, tensile strength, etc., and also readily resulting in good heat resistance. Furthermore, setting it to 5 / 95 or more provides good elongation and also facilitates good shape recovery.

[0099] The ratio (B2 / A2) is more preferably 40 / 60 or less, further preferably 35 / 65 or less, and even more preferably 30 / 70 or less; it is also more preferably 10 / 90 or more, further preferably 15 / 85 or more, and even more preferably 18 / 82 or more.

[0100] It should be noted that in this specification, the PET content (A1) and PBT content (B1) of a surface in a multilayer film refer to the PET and PBT content of the surface layer. However, in the case of this polyester film, even in the same layer as a single-layer film with a concentration gradient as described later, the PET and PBT content may vary near the surface due to variations along the thickness direction. Therefore, when the PET content varies near the surface, it is preferable to use the PET and PBT content in the region from the film surface to 5% of the overall thickness as the content (A1) and content (B1), respectively.

[0101] Furthermore, the PET content (A2) and PBT content (B2) in the central portion of the thickness direction are ideally the core layer's PET content and PBT content, respectively, in multilayer films. However, in cases where the core layer's composition varies along the thickness direction in multilayer films or in single-layer films, and where the PET content and PBT content vary along the thickness direction in the core layer or the central portion of the film's thickness direction, the PET content (A2) and PBT content (B2) in a region centered on the central portion of the film's thickness, representing 10% of the total thickness, are taken as the PET content (B2) and PBT content, respectively.

[0102] In the case where the film is, for example, a single-layer film, PET and PBT can have a concentration gradient in the thickness direction. By imparting a concentration gradient, the PET content (A1), (A2) and the PBT content (B1), (B2) can be adjusted to be within the range specified in the preferred embodiment described above.

[0103] Specifically, the PET content should have a concentration gradient that decreases from one surface of the film towards the center in the thickness direction. Furthermore, the PET content should preferably decrease from one surface towards the center in the thickness direction and then increase again towards the other surface. That is, for PET, it is sufficient to have a region with a high content (first region) and a region with a low content (second region) from one surface to the other, but it is preferable to arrange them in the order of high content region (first region), low content region (second region), and high content region (first region).

[0104] On the other hand, the PBT content should have a concentration gradient that increases from one surface of the film towards the center in the thickness direction. Furthermore, the PBT content should preferably increase from one surface towards the center of the film and then increase again towards the other surface. That is, for PBT, it is sufficient to have a region with low content (first region) and a region with high content (second region) from one surface to another, but it is preferable to arrange them in the order of low content region (first region), high content region (second region), and low content region (first region). It should be noted that for PBT, the concept of a low content region also includes regions without PBT.

[0105] (particle)

[0106] This polyester membrane may also contain particles. By containing particles, this polyester membrane can acquire properties such as slip resistance, thereby improving the membrane's operability. There are no particular limitations on the particles; examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, alumina, and titanium dioxide; cross-linked polymers such as cross-linked silicone resin particles, cross-linked acrylic resin particles, cross-linked styrene-acrylic resin particles, and cross-linked polyester particles; and organic particles such as calcium oxalate and ion exchange resins. Silica and alumina are preferred, with silica being more preferred.

[0107] Regarding the average particle size, from the viewpoint of balancing membrane transparency and operability, it is typically 0.05 μm or more and 10 μm or less, preferably 0.1 μm or more and 6 μm or less, more preferably 0.3 μm or more and 5 μm or less, and even more preferably 0.6 μm or more and 4.5 μm or less. It should be noted that the average particle size is the particle size (d50) of the cumulative volume fraction in the equivalent spherical distribution, as measured using a centrifugal sedimentation particle size distribution measuring device.

[0108] The particles can be contained throughout the entire polyester film, but are preferably contained in at least one surface of the polyester film. Therefore, in the above-described multilayer structure, it is sufficient for the particles to be contained in at least one surface layer, but when the film has surface layers on both sides, it is more preferable for the particles to be contained in both surface layers.

[0109] The particle content is not particularly limited, but is generally less than 5% by mass, preferably 0.0003% by mass or more and 3% by mass or less, more preferably 0.001% by mass or more and 2.5% by mass or less, and even more preferably 0.01% by mass or more and 1% by mass or less. When there are no particles or the particle content is low, it results in a film with excellent transparency. On the other hand, when particles are present within the above range, slipperiness is improved, resulting in good operability. Furthermore, even when particles are present, as long as the particle content is less than 5% by mass, the transparency of the film can be sufficiently ensured. It should be noted that the particle content only needs to be the above content in a region with a thickness depth of at least 1 μm from the film surface. In the case of a multilayer film structure, the particle content in the surface layer only needs to be within the above range; in the case of a single-layer structure, the particle content relative to the entire film only needs to be within the above range.

[0110] Furthermore, when the membrane has a multilayer structure, the content of particles relative to the entire membrane is preferably 0.0001% by mass or more and 2% by mass or less, more preferably 0.0005% by mass or more and 1.5% by mass or less, even more preferably 0.001% by mass or more and 1% by mass or less, and even more preferably 0.005% by mass or more and 0.7% by mass or less.

[0111] When particles are present on the surface of the polyester film, there is no particular limitation on their amount, but approximately 3 mg / m³ is preferred. 2 The above, more preferably 4 mg / m² 2 Above and 15mg / m 2 The following is a further preferred value: 5 mg / m² 2 Above and 14mg / m 2 The particles present on the surface of this polyester film may be particles that cause the particles contained in the resin constituting this polyester film to seep out, or particles that are coated on the surface of this polyester film.

[0112] In addition to the aforementioned particles, this polyester film may contain, as needed, known antioxidants, ultraviolet absorbers, antistatic agents, heat stabilizers, lubricants, dyes, pigments, and other colorants.

[0113] One or both surfaces of this polyester film can be appropriately surface-treated. Known modification treatments applied to the resin film surface, such as corona treatment or plasma treatment, are preferred as surface treatments. It should be noted that the functional layer described later can be formed on the surface of the surface-treated polyester film or on the surface of the untreated polyester film. However, surface treatment is preferably performed on the surface where the functional layer is not provided; for example, it is preferable to provide a functional layer on one surface of the polyester film and leave the other surface untreated as the corona-treated surface.

[0114] <Functional Layer>

[0115] This polyester film can have functional layers such as an easy-to-adhere layer, a release layer, an antistatic layer, an anti-blocking layer, a coating layer, a hard coating layer, an inorganic vapor-deposited layer, and a printed layer on at least one surface without impairing the effects of the present invention. Preferably, a coating layer is included, and more preferably, an easy-to-adhere layer is included. The easy-to-adhere layer is a layer provided to adhere other layers or films to the polyester film, and is not particularly limited, but is preferably formed from resins such as polyurethane-based resins, vinyl-based resins, polyamide-based resins, polyester-based resins, acrylic-based resins, and polyvinyl acetal-based resins. It is preferable to appropriately incorporate various crosslinking agents, particles, and other additives into the resin of the easy-to-adhere layer.

[0116] It should be noted that the various physical properties of this polyester film described later can be determined by measuring the polyester film with functional layers such as functional layer X.

[0117] The functional layer preferably has a mass of 1 mg / m² per unit area. 2 Above and 1000mg / m 2 The following thicknesses are used. By keeping the mass per unit area within the above range, the functional layer will not be thicker than required, and when used as functional layer X as described later, the surface free energy and / or water droplet contact angle can be easily adjusted to the desired values.

[0118] The preferred mass per unit area of ​​the functional layer is 5 mg / m². 2 Above and 500mg / m 2 The following is a further preferred value: 10 mg / m² 2 Above and 300mg / m 2 The following is a further preferred value: 15 mg / m² 2 Above and 150mg / m 2 the following.

[0119] It should be noted that the mass per unit area of ​​the functional layer can be determined by the amount of non-volatile components coated when forming the resin composition for the functional layer. In the case of drying and stretching, it is the mass per unit area of ​​the functional layer after drying and stretching. Furthermore, when functional layers are provided on both sides of the film, the mass per unit area of ​​the functional layer is the mass per unit area of ​​the functional layer provided on each surface of the film.

[0120] The thickness of the functional layer is, for example, 0.001 μm or more and 1 μm or less, preferably 0.005 μm or more and 0.5 μm or less, 0.01 μm or more and 0.4 μm or less, more preferably 0.01 μm or more and 0.3 μm or less, and even more preferably 0.01 μm or more and 0.2 μm or less. To improve slip resistance, the aforementioned particles may be included as needed.

[0121] (Functional layer X)

[0122] In one embodiment of the present invention, the functional layer is preferably a functional layer with a surface free energy of 49 mN / m or less, or a water droplet contact angle of 63° or more. For example, in the forming process of molding outer packaging materials such as soft-pack pouches, the polyester film has insufficient demolding property from the mold such as a metal mold, resulting in deformation of the molded product (battery outer packaging material) during demolding, and sometimes thickness deviation. By making the surface free energy below a certain value or the water droplet contact angle above a certain value, the functional layer can reduce the coefficient of friction (dynamic friction coefficient and static friction coefficient). Therefore, when the polyester film is placed in the mold such as a metal mold, the film will slide moderately, easily follow the mold, and the pressure can be easily applied evenly during forming, and the film can easily stretch evenly as a whole. As a result, the molded product is less prone to deformation, and it is easy to obtain a molded product with small thickness unevenness.

[0123] Functional layers having the surface free energy and / or water droplet contact angle described above are also commonly referred to as release layers. It should be noted that, hereinafter, the functional layer having the surface free energy and / or water droplet contact angle described above will be referred to as functional layer X.

[0124] From the viewpoint of reliably reducing the coefficient of friction, functional layer X is more preferably characterized by a surface free energy of 49 mN / m or less and a water droplet contact angle of 63° or more.

[0125] From the viewpoint of reducing the coefficient of friction, the surface free energy of the surface of functional layer X is more preferably 40 mN / m or less, more preferably 30 mN / m or less, and even more preferably 27 mN / m or less. Furthermore, the lower limit of the surface free energy of functional layer X is not particularly limited, but from the viewpoint that it can be easily obtained by adjusting the composition of functional layer X, for example, it is 5 mN / m or more, preferably 10 mN / m or more, and more preferably 15 mN / m or more.

[0126] Furthermore, from the viewpoint of reducing the coefficient of friction, the water droplet contact angle on the surface of functional layer X is more preferably 75° or more, further preferably 90° or more, and even more preferably 100° or more. In addition, the upper limit of the surface free energy of the surface of functional layer X is not particularly limited, for example, it is 140° or less, but from the viewpoint that it can be easily obtained by adjusting the composition of functional layer X, it is preferably 130° or less, and more preferably 120° or less.

[0127] It should be noted that, in this invention, the methods for measuring the water droplet contact angle and surface free energy are as follows.

[0128] [Method for measuring the contact angle of a water droplet]

[0129] Regarding the contact angle, a contact angle meter is used. 1 μL of pure water is dropped onto the functional layer surface of the membrane after conditioning for more than 24 hours at 23°C and 50% RH, and the contact angle is measured at this point. The contact angle is the angle 60 seconds after the water is dropped onto the membrane. It should be noted that, for example, a contact angle meter (DMo-501 model) manufactured by Kyowa Interface Science Co., Ltd. is preferred.

[0130] [Methods for determining surface free energy]

[0131] Using a contact angle meter, 1 μL of pure water and diiodomethane were added to the surface of the functional layer of the membrane after conditioning at 23°C and 50%RH for more than 24 hours, and the contact angles were measured. The contact angles were taken 60 seconds after each liquid was added to the membrane. It should be noted that the contact angles can be measured using, for example, a contact angle meter (DMo-501 model) manufactured by Kyowa Interface Science Co., Ltd. Using the obtained contact angles and the surface tension composition values ​​of each liquid shown in Table 1 below, the surface free energy of the functional layer surface of the membrane was calculated using the theoretical formula of the Owens-Wendt-Rable-Kaelble (OWRK) method.

[0132] [Table 1]

[0133]

[0134] It should be noted that surface free energy is composed of the sum of intermolecular force components. These intermolecular forces are categorized into dispersion forces, orientation forces, induction forces, and hydrogen bonds, which respectively constitute the dispersion component, polar component, induction component, and hydrogen bond component of the surface free energy. Among these components, the induction component is very weak and can therefore be ignored; the hydrogen bond component can be incorporated into the polar component.

[0135] In this specification, the surface free energy γ SVEach component (dispersion component γ) SV d and polar component γ SV p The value of γ was obtained through the following measurement and calculation methods. First, the following γ was measured... LV1 γ LV1 d and γ LV1 p The known contact angle (θ1) between the first liquid and the surface of the object being measured, and the following γ LV2 γ LV2 d and γ LV2 p The known contact angle (θ2) between the second liquid and the surface of the object being measured.

[0136] Next, substitute these values ​​into equations (I-1) and (I-2) below, and calculate the surface free energy γ of the functional layer surface of the object being measured based on the simultaneous equations (I-1) and (I-2) below. SV The dispersive component γ SV d and polar component γ SV p It should be noted that all units are in mN / m.

[0137] (γ) SV d ·γ LV1 d ) 1 / 2 +(γ) SV p ·γ LV1 p ) 1 / 2 =γ LV1 (1+cosθ1) / 2……(I-1)

[0138] (γ) SV d ·γ LV2 d ) 1 / 2 +(γ) SV p ·γ LV2 p ) 1 / 2 =γ LV2 (1+cosθ2) / 2……(I-2)

[0139] γ SV d : Measure the surface free energy γ of the object's surface SV The dispersion component.

[0140] γ SVp : Measure the surface free energy γ of the object's surface SV The polar component.

[0141] γ LV1 : Surface tension of the first liquid.

[0142] γ LV2 : Surface tension of the second liquid.

[0143] θ1: Contact angle of the first liquid.

[0144] θ2: Contact angle of the second liquid.

[0145] γ LV1 d : The dispersive component of the surface tension of the first liquid.

[0146] γ LV1 p : The polar component of the surface tension of the first liquid.

[0147] γ LV2 d : The dispersive component of the surface tension of the second liquid.

[0148] γ LV2 p : The polar component of the surface tension of the second liquid.

[0149] It should be noted that the above formulas (I-1) and (I-2) are derived from the theoretical formulas of the Owens-Wintrabel Kelboir method (OWRK) and the Young's formula.

[0150] OWRK's theoretical formula:

[0151] γ SL =γ SV +γ LV -2(γ) SV d ·γ LV d ) 1 / 2 -2(γ) SV p ·γ LV p ) 1 / 2

[0152] Young's formula:

[0153] γ SV =γ SL +γ LV ·cosθ

[0154] (wherein, γ) SLTo measure the tension at the surface of the object at the liquid interface.

[0155] There are no particular limitations on the method for adjusting the surface free energy and water droplet contact angle of the functional layer X to the aforementioned range. For example, adjustments can be made by modifying the composition and thickness of the functional layer X. When adjusting the composition of the functional layer X, for example, appropriately adjusting the types and proportions of commonly used release agents, crosslinking agents, and adhesive resins is effective. In particular, the selection of the type of release agent and the adjustment of their proportions are effective. Furthermore, if the layer contains hydrophilic groups that form weak bonds with water molecules through hydrogen bonds, such as hydroxyl, carboxyl, amide, and thiol groups, there is a tendency for the surface free energy to increase or the water droplet contact angle to decrease. Therefore, by appropriately adjusting the proportion of such hydrophilic groups, it is also easy to adjust the surface free energy or water droplet contact angle to the desired range.

[0156] In addition to the above, other methods include: adjusting the surface microstructure by physically altering it; adjusting the surface by introducing functional groups through physical and chemical treatments such as heat, light, electromagnetic, oxidation, and reduction; and adjusting the surface using surface treatment agents such as surfactants and coupling agents.

[0157] When functional layer X is provided, functional layer X can be provided on one surface of the polyester film or on two surfaces. From the viewpoint of more appropriately maximizing the effect of providing functional layer X, it is preferable that functional layer X is provided on at least one surface where the content (A1) is higher than the content (A2).

[0158] As described above, the surface of the polyester film having functional layer X has a reduced coefficient of friction due to its surface free energy being below a certain value and / or its water droplet contact angle being above a certain value. The dynamic coefficient of friction of the surface of the polyester film having functional layer X is, for example, 0.3 or less, preferably 0.25 or less, more preferably 0.2 or less, and even more preferably 0.18 or less. The lower limit of the dynamic coefficient of friction is not particularly limited, but from the viewpoint of suppressing excessive film slippage and reduced film operability when the polyester film is placed in a mold such as a metal mold, it can be 0.05, 0.08, or 0.1. Furthermore, the static coefficient of friction of the surface of the polyester film having functional layer X is, for example, 0.32 or less, preferably 0.28 or less, more preferably 0.25 or less, and even more preferably 0.23 or less. The lower limit of the static coefficient of friction is not particularly limited, but from the viewpoint of suppressing excessive film slippage and reduced film operability when the polyester film is placed in a mold such as a metal mold, it can be 0.05, 0.1, or 0.12.

[0159] It should be noted that the static friction coefficient can be measured, for example, using a translational friction testing machine (MCS-300) manufactured by Yokohama Systems Laboratories under the following test conditions. A test piece measuring 15 × 160 mm is cut from the polyester film, and the static friction coefficient between one side and the other side of the test piece is measured. Specifically, before the test begins, one side of the test piece is held in contact with the other side for 15 seconds, and the measurement is performed along the longitudinal direction (MD) under the following conditions. The sample is conditioned for at least 6 hours before the test. Then, the static friction coefficient can be measured under the following test conditions. Furthermore, the kinetic friction coefficient can be measured in the same manner as the static friction coefficient.

[0160] • Slider: Total mass 104g (contact area is a square with a side length of 12mm).

[0161] • Test speed: 20 mm / min.

[0162] Temperature: 23℃±2℃.

[0163] • Relative humidity: 50%±10%.

[0164] • Experimental values: n=12, the average of 10 points after removing the maximum and minimum values.

[0165] Functional layer X preferably contains components that function as a so-called release agent. Specifically, examples include compounds containing long-chain alkyl groups, waxes, fluorinated compounds, organosilicon compounds, etc. These release agents can be used alone or in combination.

[0166] As a release agent, compounds containing long-chain alkyl groups are preferred from the viewpoint that they are less likely to transfer to molds such as metal molds during molding and that it is easy to adjust the surface free energy and / or water droplet contact angle to the aforementioned specified values. Furthermore, in functional layer X, compounds containing long-chain alkyl groups are preferably used as the main component. When the release agent contains long-chain alkyl groups, it exhibits good compatibility with components other than the release agent in the functional layer and provides good release properties even in small quantities. It should be noted that the main component referred to here is the component with the highest proportion in the release agent. In addition to compounds containing long-chain alkyl groups, waxes, fluorinated compounds, and organosilicon compounds can also be used as release agents in functional layer X.

[0167] (Compounds containing long-chain alkyl groups)

[0168] Compounds having long-chain alkyl groups refer to compounds having straight-chain or branched alkyl groups with 4 or more carbon atoms. The alkyl group preferably has 9 or more carbon atoms, more preferably 12 or more, even more preferably 15 or more, and particularly preferably 18 or more.

[0169] By increasing the number of carbon atoms in the alkyl group as described above, functional layer X can be appropriately imparted with release properties, its surface free energy can be reduced, and / or its water droplet contact angle can be increased. There is no particular upper limit to the number of carbon atoms in the alkyl group, typically around 30, but preferably 25. Keeping the number of carbon atoms in the alkyl group below 25 is preferable from the viewpoint of solubility in solvents when used as a coating liquid (described later).

[0170] Examples of straight-chain or branched alkyl groups with 4 or more carbon atoms include: n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, neopentyl, isopentyl, hexyl, heptyl, 2-ethylhexyl, octyl, isooctyl, nonyl, isononyl, decyl, isodecyl, undecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecanyl, stearyl, isostearyl, and various octadecyl and dodecyl groups.

[0171] Examples of compounds containing long-chain alkyl groups include various polymers containing long-chain alkyl groups, amine compounds containing long-chain alkyl groups, ether compounds containing long-chain alkyl groups, and quaternary ammonium salts containing long-chain alkyl groups. From the viewpoint of exhibiting good mold release properties, polymers containing long-chain alkyl groups are preferred.

[0172] As a polymer containing long-chain alkyl groups, a polymer having long-chain alkyl groups in its side chain is preferred. Examples of methods for its manufacture include:

[0173] (1) A method of polymerizing a monomer having a long-chain alkyl group, or copolymerizing a monomer having a long-chain alkyl group with a monomer capable of copolymerizing with the monomer;

[0174] (2) A method for reacting a polymer having a reactive group with a compound having a long-chain alkyl group that can react with the reactive group, etc.

[0175] As a compound having a long-chain alkyl group, it can preferably be manufactured by the method described in (2) above.

[0176] In the method described in (1) above, the monomer having a long-chain alkyl group is preferably a (meth)acrylate monomer, for example, a (meth)acrylate having an alkyl group having 4 to 30 carbon atoms. More specifically, examples include isobutyl methacrylate, tert-butyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-heptyl methacrylate, octyl methacrylate, decyl methacrylate, dodecyl methacrylate, stearyl methacrylate, octadecyl methacrylate, isostearyl methacrylate, dodecyl methacrylate, stearyl methacrylate, and various other (meth)acrylates such as octadecyl methacrylate, isostearyl methacrylate, and dodecyl methacrylate. In this case, as described above, the alkyl group preferably has 9 or more carbon atoms, more preferably 12 or more, further preferably 15 or more, and particularly preferably 18 or more.

[0177] The long-chain alkyl-containing polymer obtained by the method described in (1) above is preferably a (meth)acrylate-based (co)polymer, and the content of the structural unit derived from the monomer having the long-chain alkyl group is preferably in the range of 10% by mass or more and 100% by mass or less. The content of the structural unit is more preferably in the range of 20% by mass or more and 80% by mass or less, and even more preferably in the range of 30% by mass or more and 60% by mass or less.

[0178] On the other hand, there are no particular limitations on the monomers that can copolymerize with monomers having long-chain alkyl groups, but (meth)acrylic acid monomers, vinyl-containing monomers, etc. are preferred.

[0179] Examples of (meth)acrylic monomers include: hydroxyl-containing monomers such as hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate; carboxyl-containing monomers such as (meth)acrylate, itaconic acid, carboxyethyl acrylate, mono(2-acryloyloxyethyl) succinate, ω-carboxy-dicaprolactone monoacrylate, and monohydroxyethyl phthalate; and alkyl (meth)acrylates other than compounds with long-chain alkyl groups that have less than 4 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, and n-propyl (meth)acrylate.

[0180] Examples of vinyl monomers include styrene, vinyl acetate, vinyl propionate, and divinylbenzene.

[0181] Among them, monomers capable of copolymerization are preferably monomers containing functional groups, such as hydroxyl-containing monomers and carboxyl-containing monomers, and preferably include carboxyl-containing monomers such as (meth)acrylic acid.

[0182] It should be noted that in this specification, (meth)acrylic acid refers to acrylic acid or methacrylic acid.

[0183] In the method described in (2) above, the reactive groups of the polymer having reactive groups can be exemplified by, for example, hydroxyl, amino, carboxyl, and acid anhydride groups. Specific examples of polymers having reactive groups include polyvinyl alcohol, polyethyleneimine, polyethyleneamine, polyester resins containing reactive groups, and poly(meth)acrylic resins containing reactive groups. Among these, from the viewpoint of mold release and ease of handling, polyvinyl alcohol and poly(meth)acrylic resins containing reactive groups are preferred, and polyvinyl alcohol is even more preferred.

[0184] To ensure the good water solubility of compounds containing long-chain alkyl groups, the reactive groups can be neutralized. Stabilizers can be used to neutralize these reactive groups. Examples of basic stabilizers include inorganic basic compounds such as calcium hydroxide, magnesium hydroxide, lithium hydroxide, potassium hydroxide, and sodium hydroxide; and amine compounds such as ammonia, trimethylamine, triethylamine, diethylamine, and dimethylaminoethanol. Among these, inorganic basic compounds are preferred, specifically calcium hydroxide, magnesium hydroxide, and lithium hydroxide.

[0185] Examples of compounds containing long-chain alkyl groups that can react with the reactive groups include: various octadecyl isocyanates such as octyl isocyanate, decyl isocyanate, dodecyl isocyanate, isostearyl isocyanate, stearyl isocyanate, etc.; acyl chlorides containing long-chain alkyl groups such as hexanoyl chloride, octanoyl chloride, decanoyl chloride, lauroyl chloride, octadecanoyl chloride, docosanoyl chloride; amines containing long-chain alkyl groups; and alcohols containing long-chain alkyl groups. Among these, isocyanates containing long-chain alkyl groups are preferred from the viewpoint of mold release and ease of handling, and stearyl isocyanate is particularly preferred.

[0186] The number average molecular weight (Mn) of the long-chain alkyl-containing polymers obtained by the methods described in (1) and (2) above is preferably 1,000 or more and 100,000 or less, more preferably 2,000 or more and 80,000 or less. When these number average molecular weights are above the lower limit, by reducing the low molecular weight components in the functional layer X, the long-chain alkyl portion can be efficiently biased to exist on the surface of the functional layer, thereby obtaining sufficient release properties. On the other hand, when these number average molecular weights are below the upper limit, they are easily soluble in the solvent contained in the coating liquid, which is a preferred method for the resin composition of the functional layer, and are easily coated onto the polyester film.

[0187] The melting point of the compound containing long-chain alkyl groups is preferably above 0°C and below 100°C, more preferably above 10°C and below 100°C, and even more preferably above 20°C and below 90°C.

[0188] (wax)

[0189] As for waxes, examples include natural waxes, synthetic waxes, and waxes that combine them.

[0190] Natural waxes include plant-based waxes, animal-based waxes, mineral-based waxes, and petroleum waxes. Examples of plant-based waxes include candelilla wax, carnauba wax, rice bran wax, wood wax, and jojoba oil. Examples of animal-based waxes include beeswax, lanolin, and whale wax. Examples of mineral-based waxes include lignite wax, ceresin wax, and pure ceresin wax. Examples of petroleum waxes include paraffin wax, microcrystalline wax, and petrolatum.

[0191] Synthetic waxes can include synthetic hydrocarbons, modified waxes, hydrogenated waxes, fatty acids, fatty acid amides, amines, imides, ester waxes, and ketones.

[0192] Examples of synthetic hydrocarbons include Fischer-Tropsch wax (Sasol wax), polyethylene wax, oxidized polyethylene wax, and oxidized polypropylene wax. They also include low molecular weight polymers (number average molecular weight 500–20,000), specifically polypropylene, ethylene-acrylic acid copolymers, polyethylene glycol, polypropylene glycol, and block or graft copolymers of polyethylene glycol and polypropylene glycol.

[0193] Examples of modified waxes include lignite wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives. Here, "derivative" refers to compounds obtained through any one of the following processes: refining, oxidation, esterification, saponification, or a combination thereof.

[0194] Examples of hydrogenated waxes include hydrogenated castor oil and hydrogenated castor oil derivatives.

[0195] Among these waxes, synthetic waxes are preferred from the viewpoint of excellent release properties and easy availability, synthetic hydrocarbon waxes are more preferred, and oxidized polyethylene waxes and oxidized polypropylene waxes are even more preferred. It should be noted that, from the viewpoint of efficiently attracting long-chain alkyl portions to the surface of functional layer X by reducing low molecular weight components in functional layer X, the number average molecular weight (Mn) of the wax is preferably in the range of 1,000 or more and 100,000 or less, and the weight average molecular weight (Mw) is preferably in the range of 2,000 or more and 80,000 or less.

[0196] Considering factors such as durability during heat treatment, the melting point or softening point of the wax is preferably 80°C or higher, more preferably 110°C or higher. From the viewpoint of controlling the demolding performance after heat treatment, it is preferably 200°C or lower, more preferably 170°C or lower, and even more preferably 150°C or lower. It should be noted that the melting point or softening point of the wax can be determined by differential scanning calorimetry (DSC).

[0197] (Fluorine compounds)

[0198] As a fluorine compound, any polymer containing fluorine atoms within its molecule is acceptable. Examples include polymers containing perfluoroalkyl groups and polymers of olefins containing fluorine atoms. From the perspective that a low content is sufficient to demonstrate good mold release properties, polymers containing perfluoroalkyl groups are preferred.

[0199] As monomers for forming polymers containing perfluoroalkyl groups, perfluoroalkyl (meth)acrylates, vinyl ethers, etc., are preferred.

[0200] Examples of perfluoroalkyl (meth)acrylates include: perfluoroalkyl (meth)acrylate, perfluoroalkyl methyl (meth)acrylate, 2-perfluoroalkyl ethyl (meth)acrylate, 3-perfluoroalkyl propyl (meth)acrylate, 3-perfluoroalkyl-1-methylpropyl (meth)acrylate, 3-perfluoroalkyl-2-propylene (meth)acrylate, etc.

[0201] In addition, examples of vinyl ethers containing perfluoroalkyl groups include: perfluoroalkyl methyl vinyl ether, 2-perfluoroalkyl ethyl vinyl ether, 3-perfluoropropyl vinyl ether, 3-perfluoroalkyl-1-methylpropyl vinyl ether, 3-perfluoroalkyl-2-propenyl vinyl ether, etc.

[0202] They can be polymerized individually or in combination. Furthermore, from the viewpoint that release properties can be achieved with a low content, the number of carbon atoms in the perfluoroalkyl group is preferably 3 to 11.

[0203] It should be noted that, from the viewpoint of efficiently biasing the long-chain alkyl portion to the surface of the functional layer X by reducing the low molecular weight components in the functional layer X, the number average molecular weight (Mn) of the fluorine compound (polymer) is preferably in the range of 1,000 or more and 100,000 or less, and the weight average molecular weight (Mw) is preferably in the range of 2,000 or more and 80,000 or less.

[0204] (Organosilicon compounds)

[0205] Organosilicon compounds are compounds with intramolecular siloxane bonds (-Si-O-), including: organosilicon emulsions, acrylic-grafted organosilicon, organosilicon-grafted acrylic acid, amino-modified organosilicon, perfluoroalkyl-modified organosilicon, and alkyl-modified organosilicon. Considering factors such as mold release properties and heat resistance, cured organosilicon resins are preferred.

[0206] As for types of curable silicone resins, examples include addition type, condensation type, UV curable type, electron beam curable type, etc., and any curing type can be used.

[0207] It should be noted that, from the viewpoint of efficiently biasing the long-chain alkyl portion to the surface of the functional layer X by reducing the low molecular weight components in the functional layer X, the number average molecular weight (Mn) of the organosilicon compound is preferably in the range of 100 or more and 100,000 or less, and the weight average molecular weight (Mw) is preferably in the range of 200 or more and 80,000 or less.

[0208] (Cross-linking agent)

[0209] Regarding functional layer X, i.e., the resin composition for the functional layer described later, it is preferable to further contain a crosslinking agent. Examples of crosslinking agents include melamine compounds, oxazoline compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, and silane coupling agents. Among these crosslinking agents, melamine compounds are preferred from the viewpoint of maintaining good mold release properties and having high crosslinking density and elastic modulus. Therefore, functional layer X, i.e., the resin composition for the functional layer described later, preferably contains a compound containing long-chain alkyl groups and a crosslinking agent, and more preferably contains a compound containing long-chain alkyl groups and a melamine compound.

[0210] A crosslinking agent is a substance that reacts with a release agent, such as a compound containing long-chain alkyl groups, to improve the performance of the release layer. Therefore, in functional layer X, the crosslinking agent preferably reacts with a release agent such as a compound containing long-chain alkyl groups. By using a crosslinking agent, the release agent, such as a compound containing long-chain alkyl groups, can be effectively biased towards the surface of functional layer X, thereby easily reducing the surface free energy and further improving the water droplet contact angle. The crosslinking agent can be considered to exist in functional layer X in either the form of an unreacted substance or a reacted compound.

[0211] Melamine compounds are compounds having a melamine backbone. Examples include hydroxyalkylated melamine derivatives, compounds partially or completely etherified by reacting an alcohol with a hydroxyalkylated melamine derivative, and mixtures thereof. Methanol, ethanol, isopropanol, n-butanol, and isobutanol are preferred alcohols for etherification. Furthermore, melamine compounds can be monomers, polymers of two or more monomers, or mixtures thereof. Additionally, substances co-condensed with a portion of melamine, such as urea, can be used. To improve the reactivity of the melamine compound, a catalyst can also be used.

[0212] Examples of hydroxyalkylation include hydroxymethylation, hydroxyethylation, hydroxyisopropylation, hydroxyn-butylation, and hydroxyisobutylation. From a reactivity point of view, hydroxymethylation is preferred. From the viewpoint of improving coating strength and the adhesion between functional layer X and the polyester film, the melamine compound is preferably a partially etherified hydroxyalkylated melamine derivative, more preferably a hydroxyalkylated melamine etherified with methanol. Therefore, a more preferred method is a partially etherified melamine having both hydroxymethyl and methoxy groups.

[0213] The etherified hydroxyalkyl group is preferably 0.5 equivalents or more and 5 equivalents or less relative to the unetherified hydroxyalkyl group, more preferably 0.7 equivalents or more and 3 equivalents or less, and even more preferably 1.2 equivalents or more and 2.8 equivalents or less. Furthermore, the melamine compound can be any of a monomer, a dimer or more polymer, or a mixture thereof. Moreover, a substance co-condensed with urea or similar substances can be used, and a catalyst can be used to improve the reactivity of the melamine compound.

[0214] Oxazoline compounds are compounds containing an oxazoline group within their molecules, with polymers containing an oxazoline group being particularly preferred. Polymers containing an oxazoline group can be synthesized by homopolymerization of monomers containing an oxazoline group or by polymerization with other monomers. Examples of monomers containing an oxazoline group include: 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.

[0215] Epoxy compounds are compounds that have epoxy groups in their molecules. Examples include condensates of epichlorohydrin with hydroxyl and amino groups of compounds such as ethylene glycol, polyethylene glycol, glycerol, polyglycerol, and bisphenol A. These compounds include polyepoxy compounds, diepoxy compounds, monoepoxy compounds, and glycidylamine compounds.

[0216] Examples of isocyanate compounds include: toluene diisocyanate compounds such as 2,4-toluene diisocyanate and 2,6-toluene diisocyanate; phenyl diisocyanate compounds such as 1,3-phenylenedimethylene diisocyanate, 1,4-phenylenedimethylene diisocyanate and tetramethylphenylenedimethylene diisocyanate; aromatic isocyanate compounds such as 1,5-naphthalene diisocyanate and triphenylmethane triisocyanate; hexamethylene diisocyanate, isophorone diisocyanate, and adducts of these isocyanate compounds with polyols such as trimethylolpropane, biuret forms of these polyisocyanate compounds, and isocyanurate forms.

[0217] Examples of carbodiimide compounds include: dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, diphenylcarbodiimide, ditert-butylcarbodiimide, di-β-naphthylcarbodiimide, and other monocarbodiimide compounds; and isocyanate-terminated polycarbodiimides obtained by condensation reactions accompanying the decarbonylation of diisocyanates.

[0218] Examples of silane coupling agents include: γ-mercaptopropyltrimethoxysilane, γ-isocyanate propyltriethoxysilane, γ-isocyanate propyltrimethoxysilane, and N-(1,3-dimethylbutylene)-3-(triethoxysilyl)-1-propylamine.

[0219] As described above, functional layer X preferably contains a compound containing long-chain alkyl groups and a crosslinking agent. In this case, in functional layer X (resin composition for functional layer), the proportion of the compound containing long-chain alkyl groups relative to all non-volatile components is preferably 5% by mass or more and 95% by mass or less, and the proportion of the crosslinking agent is preferably 5% by mass or more and 95% by mass or less.

[0220] When the content of the long-chain alkyl compound is 5% by mass or more, the functional layer X can be appropriately imparted with mold release properties, the surface free energy of the functional layer surface can be easily set to a certain level or below, and the water droplet contact angle can be easily adjusted to a specified value or above. By making the content of the long-chain alkyl compound 95% by mass or less, it is easy to include components other than the long-chain alkyl compound, such as crosslinking agents, in an appropriate amount in the functional layer X. The content of the long-chain alkyl compound is more preferably 15% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 70% by mass or less, and even more preferably 40% by mass or more and 65% by mass or less.

[0221] Furthermore, when the crosslinking agent content is 5% by mass or more, the functional layer X can be appropriately crosslinked by the crosslinking agent, thereby improving the performance of the functional layer X and easily adjusting the surface free energy and water droplet contact angle of the functional layer surface to the desired values. By keeping the crosslinking agent content at 95% by mass or less, it is easy to include components other than the crosslinking agent, such as compounds containing long-chain alkyl groups, in the functional layer X in appropriate amounts.

[0222] The crosslinking agent is preferably contained in a proportion of 10% or more and 80% or less by mass, more preferably 20% or more and 70% or less by mass, and even more preferably 30% or more and 50% or less by mass.

[0223] Functional layer X, i.e., the resin composition for the functional layer, may also contain components other than release agents and crosslinking agents, such as adhesive resins. Adhesive resins readily impart film-forming properties to functional layer X.

[0224] There are no particular limitations on the adhesive resin used; known adhesive resins can be used, such as polyester resins, (meth)acrylic resins, polyurethane resins, polyvinyl alcohol (polyvinyl alcohol, vinyl chloride-vinyl acetate copolymer, etc.), polyalkylene glycols, polyalkylimides, methylcellulose, hydroxycellulose, starches, etc. From the viewpoint of moldability and adhesion to the polyester film, at least one selected from polyester resins, (meth)acrylic resins, and polyurethane resins is preferred. One adhesive resin can be used alone, or two or more can be used in combination.

[0225] (additive)

[0226] In addition to the above-mentioned components, functional layer X, i.e., the resin composition for the functional layer, may further contain particles and additives. The particles are added to improve anti-blocking and slip properties, and their type, shape, average particle size, and content are the same as those of the particles that can be incorporated into the polyester film. Furthermore, examples of additives include: antistatic agents, ultraviolet absorbers, antioxidants, defoamers, lubricants, foaming agents, dyes, and pigments.

[0227] Functional layer X is formed on at least one side of the polyester film using a functional layer resin composition. The functional layer resin composition contains a release agent such as the compound having long-chain alkyl groups, and preferably further contains a crosslinking agent. The functional layer resin composition may also, as needed, contain adhesive resins, particles, other additives, and solvents. The functional layer resin composition is particularly preferably a coating liquid containing a solvent.

[0228] When the coating liquid is prepared, the concentration of the solid component of the composition is preferably 0.1% by mass or more and 50% by mass or less, more preferably 0.5% by mass or more and 40% by mass or less, and even more preferably 1% by mass or more and 30% by mass or less.

[0229] The resin composition for the functional layer is preferably prepared as a liquid coating solution containing a solvent, applied to the surface of a polyester film, dried and cured as needed, to form the functional layer X. In the coating solution, the components forming the functional layer X can be dissolved or dispersed in the solvent. Furthermore, in the resin composition for the functional layer, the solvent is a volatile component.

[0230] As a solvent, either water or an organic solvent, or a mixture of water and an organic solvent, can be used. Examples of organic solvents include: aromatic hydrocarbons such as toluene; aliphatic hydrocarbons such as hexane, heptane, and isooctane; esters such as ethyl acetate and butyl acetate; ketones such as ethyl methyl ketone and isobutyl methyl ketone; alcohols such as ethanol and 2-propanol; and ethers such as diisopropyl ether and dibutyl ether. One organic solvent can be used alone, or two or more can be used in combination.

[0231] (Surface roughness (Ra))

[0232] The surface roughness (Ra) of functional layer X is not particularly limited, but is, for example, 1 nm or more and 100 nm or less, preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 30 nm or less. By ensuring that the surface roughness (Ra) of functional layer X is within the above range, the polyester film will slide moderately when placed in a mold such as a metal mold, resulting in good processability. Furthermore, it exhibits good smoothness when rolled out of the film when laminated with other films, thus tending to have excellent operability.

[0233] It should be noted that surface roughness (Ra) is an arithmetic mean roughness, one of the linear roughness parameters (JIS B0601:1994), representing the average height difference from the average surface. Specifically, when a portion of reference length L is extracted, and the average line of this extracted portion is taken as the x-axis and the longitudinal scaling direction as the y-axis, the roughness curve is expressed as y=Z(x), which is then calculated using the following formula.

[0234] [Formula 1]

[0235]

[0236] <Heat Shrinkage Rate>

[0237] After heat treatment at 160°C for 15 minutes, the thermal shrinkage rate of this polyester film is less than 5% in either the longitudinal or transverse direction, and greater than 2.5% in the other direction.

[0238] If the heat shrinkage rate of one side of this polyester film is less than 5%, it exhibits excellent heat resistance. Therefore, dimensional deformation is reduced when it is laminated onto other components such as films through lamination processes, and it is easy to laminate onto other films. Furthermore, shrinkage stress is less likely to remain after lamination onto other films, preventing shrinkage during secondary processing into battery packaging materials, resulting in good reprocessability. Consequently, even if the battery releases heat and the battery packaging material is heated, it is easy to prevent deterioration of the packaging material.

[0239] On the other hand, if the thermal shrinkage rate in the other direction is greater than 2.5%, the heated film will shrink by a certain amount, for example, in the laminate, the adhesion with other components such as the metal layer is good.

[0240] From the viewpoint of achieving good heat resistance, the heat shrinkage rate in the aforementioned one direction is preferably 4.5% or less, more preferably 4% or less, even more preferably 3.5% or less, and even more preferably 3% or less. While a lower heat shrinkage rate in the aforementioned one direction is preferable from the viewpoint of heat resistance, it is preferable to have a certain value or higher from the viewpoint of achieving good adhesion to the metal layer, etc., for example, 0.1% or more, preferably 0.5% or more, and even more preferably 1% or more.

[0241] Furthermore, from the viewpoint of ensuring good adhesion to the metal layer, the heat shrinkage rate in the other direction is more preferably 3% or more, further preferably 3.5% or more, and even more preferably 3.7% or more. Additionally, the heat shrinkage rate in the other direction is preferably 9% or less, more preferably 8% or less, further preferably 7% or less, even more preferably 6% or less, and even more preferably 5.5% or less. Besides the heat shrinkage rate in one direction, when the heat shrinkage rate in the other direction is also below a certain value, the heat resistance of the film is further improved. Therefore, it is easy to laminate onto other films by lamination, and secondary processing properties are also good.

[0242] Furthermore, in this polyester film, the ratio of longitudinal heat shrinkage rate to transverse heat shrinkage rate (MD / TD) is not particularly limited, for example, it is 0.4 or more and 10 or less, preferably 0.6 or more and 8 or less, more preferably 0.8 or more and 6 or less, even more preferably 1 or more and 4 or less, and even more preferably 0.7 or more and 2 or less. If the above ratio (MD / TD) is within the above range, it can achieve good adhesion to metal layers, etc., and further improve heat resistance, making it easy to laminate onto other films in lamination processes, etc., and thus also improving secondary processing properties. The heat shrinkage rate ratio (MD / TD) is more preferably 0.8 or more and 1.8 or less, and even more preferably 1.0 or more and 1.7 or less.

[0243] It should be noted that the heat shrinkage rate can be appropriately adjusted by adjusting the stretching conditions and heat setting temperature of the polyester film described later.

[0244] It should be noted that the longitudinal direction of the membrane refers to the MD (machine direction), which is the direction in which the membrane travels during the membrane manufacturing process, i.e., the winding direction of the membrane roll. The transverse direction of the membrane refers to the TD (transverse direction), which is the direction parallel to the membrane surface and orthogonal to the longitudinal direction, i.e., the direction parallel to the central axis of the roll when it is made into a membrane roll.

[0245] <Endothermic peak>

[0246] This polyester film preferably has only one endothermic peak at temperature, as determined by differential scanning calorimetry (DSC), and more preferably, only one melting peak from both the first and second temperature-increasing scans. When there is only one endothermic peak, the polyester film is less prone to softening at low temperatures. Therefore, when used for battery packaging, even if the battery releases heat and heats the packaging material, it is easier to prevent the packaging material from deteriorating. Furthermore, when performing secondary processing such as shaping, if there are two endothermic peaks, either the processing temperature corresponding to the low-temperature side peak or the processing temperature corresponding to the high-temperature side peak must be used. If the processing temperature corresponds to the low-temperature side peak, shaping is performed while the resin at the high-temperature side peak is not melted, reducing the shapeability. Conversely, if the processing temperature corresponds to the high-temperature side peak, the resin at the low-temperature side peak undergoes dimensional changes before reaching the processing temperature, sometimes resulting in wrinkles due to shrinkage. Therefore, by molding with only one endothermic peak in this polyester film, it is also advantageous to further improve secondary processing properties such as shapeability. Furthermore, even by increasing the heat setting temperature in the manufacturing method described later, mold making can be stabilized, thus making it easy to adjust the heat shrinkage rate. It should be noted that by making PBT and PET compatible, the polyester film can be adjusted to have only one endothermic peak.

[0247] It should be noted that the single endothermic peak may have a shoulder peak at its tail, but the case in which two or more endothermic peaks originating from PBT and PET are clearly observed is excluded.

[0248] Melting point

[0249] The melting point (Tm) of the polyester film obtained by differential scanning calorimetry (DSC) for the first temperature scan is preferably 230°C or higher. When the melting point (Tm) of the first temperature scan is 230°C or higher, the heat resistance is good, and the thermal shrinkage rate is easily reduced. The melting point (Tm) of the polyester film for the first temperature scan is preferably 235°C or higher, more preferably 240°C or higher. Furthermore, from the viewpoint of easily maximizing the effects of using PBT, the melting point (Tm) of the polyester film for the first temperature scan is preferably 260°C or lower, more preferably 255°C or lower, further preferably 252°C or lower, and even more preferably 250°C or lower.

[0250] The melting point (Tm) of the polyester film obtained by differential scanning calorimetry (DSC) for the second temperature scan is not particularly limited, but is preferably 223°C or higher. When the melting point (Tm) of the second temperature scan is 223°C or higher, the heat resistance is good, and the thermal shrinkage rate is easily reduced. The melting point (Tm) of the second temperature scan of this polyester film is preferably 228°C or higher, more preferably 233°C or higher. Furthermore, from the viewpoint of easily maximizing the effects of using PBT, the melting point (Tm) of the second temperature scan of this polyester film is preferably 255°C or lower, more preferably 250°C or lower, further preferably 247°C or lower, and even more preferably 243°C or lower.

[0251] Melting point (Tm) was determined according to JIS K7121:2012 under conditions of -70 to 280 °C, heating rate of 10 °C / min, and cooling rate of 600 °C / min. The peak value of the endothermic peak observed during the first heating was taken as the melting point of the first heating scan, and the peak value of the endothermic peak observed during the second heating was taken as the melting point of the second heating scan.

[0252] Glass transition temperature (Tg)

[0253] The glass transition temperature (Tg) of this polyester film, as determined by differential scanning calorimetry, is not particularly limited, but is preferably 50°C or higher, more preferably 55°C or higher, and even more preferably 60°C or higher. When the glass transition temperature (Tg) is above a certain value, the heat resistance is good, and the thermal shrinkage rate is easily reduced. The glass transition temperature (Tg) of this polyester film is not particularly limited, but is preferably 80°C or lower, more preferably 75°C or lower, and even more preferably 70°C or lower.

[0254] The glass transition temperature (Tg) was determined according to JIS K7121:2012 under the conditions of -70 to 280℃, heating rate of 10℃ / min, and cooling rate of 600℃ / min, and the midpoint glass transition temperature at the reheating point was used.

[0255] The absolute value of the difference between the transverse orientation degree (Δnv) and the longitudinal orientation degree (Δnp) of this polyester film (|Δnv-Δnp|) is, for example, 75 or less, preferably 57 or less. As described above, this polyester film, based on the presence of PBT and PET, achieves excellent puncture resistance by reducing |Δnv-Δnp|. Specifically, it exhibits less displacement and less unevenness in puncture strength, and more uniform elongation in the thickness direction, making it more suitable for outer packaging material applications.

[0256] From the viewpoint of puncture resistance, |Δnv-Δnp| is preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less.

[0257] Furthermore, |Δnv-Δnp| is not particularly limited, as long as it is 0 or above, but in practical applications it can be 5 or above, preferably 10 or above, and more preferably 15 or above.

[0258] The planar orientation degree (ΔP) of this polyester film is preferably 100 or more, more preferably 120 or more, even more preferably 140 or more, and even more preferably 150 or more. When the planar orientation degree of this polyester film is a certain value or above, the crystallinity of the film is improved, which makes it easier to improve the puncture strength. In addition, the planar orientation degree is not particularly limited, but it is preferably 200 or less, more preferably 180 or less, and even more preferably 170 or less.

[0259] Furthermore, this polyester film typically has a transverse orientation degree (Δnv) greater than a longitudinal orientation degree (Δnp). The transverse orientation degree (Δnv) is not particularly limited, but is, for example, 50 or more and 130 or less, preferably 60 or more and 120 or less, more preferably 70 or more and 110 or less, and even more preferably 75 or more and 105 or less. Similarly, the longitudinal orientation degree (Δnp) is not particularly limited, but is, for example, 20 or more and 100 or less, preferably 30 or more and 90 or less, more preferably 40 or more and 80 or less, and even more preferably 45 or more and 70 or less.

[0260] The |Δnv-Δnp|, transverse orientation (Δnv), longitudinal orientation (Δnp), and planar orientation (ΔP) of this polyester film can be set to the above range by adjusting the stretching ratio, stretching temperature, preheating temperature and time, and heat setting temperature and time during the manufacturing process of this polyester film.

[0261] The face orientation degree (ΔP), longitudinal orientation degree (Δnp), and transverse orientation degree (Δnv) of this polyester film can be calculated as follows.

[0262] The longitudinal refractive index (nx), transverse refractive index (ny), and thickness refractive index (nz) of this polyester film were determined using an Abbe refractometer with sodium D line as the light source, according to JIS K 7142-2014 5.1 (Method A). The planar orientation degree (also known as the planar orientation coefficient; ΔP), longitudinal orientation degree (also known as the longitudinal planar orientation coefficient; Δnp), and transverse orientation degree (also known as the transverse planar orientation coefficient; Δnv) can be calculated by substituting the measurement results into the following formula.

[0263] ΔP=((nx+ny) / 2-nz)×1000

[0264] Δnp=(nx-(ny+nz) / 2)×1000

[0265] Δnv=(ny-(nx+nz) / 2)×1000

[0266] <Puncture strength>

[0267] The puncture strength of this polyester film is preferably 480 N / mm or higher. A puncture strength of 480 N / mm or higher results in high puncture resistance, making it suitable for battery packaging applications. More preferably, the puncture strength is 490 N / mm or higher, even more preferably 500 N / mm or higher, even more preferably 510 N / mm or higher, even more preferably 520 N / mm or higher, and even more preferably 530 N / mm or higher. The puncture strength is not particularly limited, but for example, it can be 1000 N / mm or lower, preferably 800 N / mm, more preferably 700 N / mm or lower, even more preferably 650 N / mm or lower, even more preferably 590 N / mm or lower, even more preferably 585 N / mm or lower, even more preferably 580 N / mm or lower, and even more preferably 575 N / mm or lower. When the puncture strength is below the above-mentioned upper limit, the polyester film exhibits good elongation. Furthermore, by setting the puncture strength below the aforementioned upper limit, for example when manufacturing actual products such as battery packaging materials through shaping and molding, there is a tendency to suppress the restoring force of the film attempting to return to its original shape, thus easily improving the shape retention of the actual product. For example, it is possible to more effectively suppress deformation of the packaging material caused by post-processing such as heat welding or by heat generation from internally housed energy storage components.

[0268] <Displacement during puncture>

[0269] Furthermore, the displacement during puncture of this polyester film is preferably 4 mm or more. If the displacement during puncture is 4 mm or more, it exhibits good elongation, allowing for sufficient stretching even during forming and molding, and facilitating an increase in molding depth. More preferably, the displacement during puncture is 4.2 mm or more, and even more preferably 4.3 mm or more. The displacement during puncture is not particularly limited; for example, it can be 8 mm or less, 6 mm or less, or 5 mm or less.

[0270] Uneven puncture intensity

[0271] The coefficient of variation of the puncture strength of this polyester film is preferably 0.036 or less, more preferably 0.034 or less, even more preferably 0.032 or less, even more preferably 0.03 or less, even more preferably 0.028 or less, even more preferably 0.026 or less, even more preferably 0.024 or less, even more preferably 0.022 or less, and even more preferably 0.02 or less. By reducing the coefficient of variation, this polyester film also reduces the unevenness of puncture strength and makes the elongation in the thickness direction more uniform, making it suitable for use as a battery packaging material. A lower coefficient of variation for puncture strength is better, but in practical applications, it is preferably 0.001 or more, more preferably 0.005 or more, and even more preferably 0.01 or more.

[0272] It should be noted that the coefficient of variation of puncture intensity represents the non-uniformity of puncture intensity and is calculated from the standard deviation / mean value. Furthermore, the mean value and standard deviation are the average and standard deviation of the measured values ​​(puncture intensity) at 12 points in this polyester film sample. It should also be noted that the coefficient of variation of displacement during puncture, described later, represents the non-uniformity of displacement during puncture; it can be calculated similarly, except by changing the measured values ​​to the displacement during puncture.

[0273] Uneven displacement during puncture

[0274] The coefficient of variation of displacement during puncture of this polyester film is preferably 0.034 or less, more preferably 0.03 or less, even more preferably 0.027 or less, even more preferably 0.025 or less, even more preferably 0.023 or less, even more preferably 0.021 or less, and even more preferably 0.019 or less. By reducing the coefficient of variation of displacement during puncture, this polyester film reduces the unevenness of displacement and makes the elongation in the thickness direction more uniform, making it suitable for battery packaging materials. Furthermore, it can be uniformly stretched during forming, resulting in good formability. A lower coefficient of variation of displacement during puncture is better, but in practical applications, it is preferably 0.001 or more, more preferably 0.005 or more, and even more preferably 0.01 or more.

[0275] <Madall hardness>

[0276] The preferred Martens hardness of this polyester film is 132 N / mm. 2 The above is preferred, with 135 N / mm being more ideal. 2 The above is further optimized to 138 N / mm. 2 In conclusion, when the martensitic hardness reaches a certain level, properties such as pinhole resistance and fracture strength tend to improve. There is no specific upper limit to the martensitic hardness; for example, it can be 300 N / mm². 2 It can also be 200 N / mm 2 .

[0277] <Indentation Hardness>

[0278] The preferred indentation hardness of this polyester film is 200 N / mm. 2 The above is preferred, with 210 N / mm. 2 The above is further optimized to 215 N / mm. 2 The above applies. When the indentation hardness reaches a certain level, resistance to pinholes and fracture strength are easily improved. There is no specific upper limit to the indentation hardness; for example, it can be 400 N / mm². 2 It can also be 300 N / mm 2 .

[0279] <Elastic Deformation Power>

[0280] The elastic deformation power of this polyester film is preferably 42% or more, more preferably 43% or more, and even more preferably 44% or more. By setting the elastic deformation power to a certain level or higher, it is easy to obtain molded products with excellent design flexibility and shape recovery. The upper limit of the elastic deformation power of this polyester film is not particularly limited, for example, it can be 60%, 57%, 53%, or 50%.

[0281] It should be noted that the martensitic hardness, indentation hardness, and elastic deformation power are acceptable as long as the values ​​measured on at least one surface of the polyester film are above the aforementioned lower limit. Specifically, the values ​​measured on the surface of the polyester film where the PET content (A1) is greater than the content (A2) in the central part of the film are acceptable as long as they are above the aforementioned lower limit, but it is preferable that the values ​​measured on both surfaces are above the aforementioned lower limit. Furthermore, the martensitic hardness, indentation hardness, and elastic deformation power can be determined by performing a micro-hardness test on the surface of the polyester film, using a load-unloading test when an indenter is pressed in at 20 mN. Specifically, this can be determined using the method described in the examples described later.

[0282] <Haze>

[0283] The haze of this polyester film can be, for example, 20% or less, and transparency can be ensured by reducing the value. Therefore, the haze of this polyester film is preferably 10% or less, more preferably 8% or less, even more preferably 5% or less, and particularly preferably 3% or less. The haze is not particularly limited, for example, it can be 0.01% or more, 0.1% or more, or 0.7% or more.

[0284] Intrinsic viscosity

[0285] The intrinsic viscosity of this polyester film is preferably 0.6 dL / g or higher and 0.85 dL / g or lower. When the intrinsic viscosity of this polyester film is within the above range, it is easy to achieve good productivity and moldability. More preferably, the intrinsic viscosity of this polyester film is 0.62 dL / g or higher and 0.8 dL / g or lower; even more preferably, it is 0.63 dL / g or higher and 0.78 dL / g or lower; and even more preferably, it is 0.64 dL / g or higher and 0.75 dL / g or lower.

[0286] [Manufacturing method of polyester film]

[0287] Next, taking the case where the polyester film is a biaxially stretched polyester film as an example, the manufacturing method of the polyester film (hereinafter sometimes simply referred to as "this manufacturing method") will be described. In the case where the polyester film is a biaxially stretched polyester film, it is preferable to first manufacture an unstretched sheet, and then stretch it in two directions to obtain a biaxially stretched polyester film.

[0288] The unstretched sheet is preferably obtained as follows: the PET and PBT, along with other resins, particles, and other additives as needed, are fed into an extruder, appropriately mixed, and extruded from a die as a molten sheet using the extruder, then cooled and solidified using a cooling roller. In this case, to improve the flatness of the sheet, it is preferable to improve the adhesion between the sheet and the cooling roller, preferably by using an electrostatic application method and / or a liquid coating method. Furthermore, it is preferable to mix PET and PBT in a compatible manner in the extruder, specifically, it is preferable to mix at 270–300°C, preferably 275–295°C, and more preferably 280–290°C.

[0289] In addition, compatibilizers can be used to improve compatibility. Suitable compatibilizers can be selected from those commonly used in PBT and PET.

[0290] When using an extruder for compounding, it is sufficient to ensure that PBT and PET are compatible through thorough compounding. For example, an extruder with a screw length L (mm) to screw diameter D (mm), i.e., L / D, is preferably 15 or more, more preferably 20 or more, and further preferably 50 or less, more preferably 40 or less. Using such an extruder easily improves the compatibility of PBT and PET, prevents prolonged resin residence time or excessively high resin temperature, and easily suppresses film discoloration associated with thermal degradation, degassing during molding, and the formation of gel-like foreign matter. Regarding the screw configuration of the extruder, a structure having a kneading unit, particularly a helical kneading unit, is preferred to improve compounding properties. One or two kneading units are preferred.

[0291] A continuous kneader with fixed blades installed in the cylinder of an extruder, which is freely mounted on a screw that rotates within the cylinder of an extruder, is also effective as a mixing machine when it is inserted between these multiple rotating blades.

[0292] Furthermore, adjusting the ratio Q / N of the discharge rate Q (kg / hr) to the screw speed N (rpm) during melt mixing is also effective. Q / N is preferably 0.1 or more, more preferably 0.2 or more; further preferably 10 or less, more preferably 6 or less, and even more preferably 4 or less. By setting Q / N within the above range, film discoloration and foreign matter generation caused by excessively high resin temperature or excessively long residence time can be suppressed, and PBT and PET can be easily made fully compatible.

[0293] Furthermore, it is also effective to make the melt viscosity of PBT and PET similar. Melt viscosity can be controlled by molecular weight and branching structure.

[0294] Furthermore, the temperature of the cooling roller is preferably 10–40°C, more preferably 15–35°C, and even more preferably 20–30°C. To improve the flatness of the sheet, it is preferable to improve the adhesion between the sheet and the rotating cooling roller. As described above, electrostatic application or liquid coating application methods are preferably appropriate.

[0295] Furthermore, when the polyester film has a multilayer structure, it is preferable to co-extrude the multilayers to produce an unstretched sheet with a multilayer structure. Additionally, it is preferable to feed the polyester as raw material to the extruder after appropriate drying in the form of granules or the like. Furthermore, particles and other additives can also be appropriately incorporated into the granules.

[0296] In the case where the polyester film is a single-layer film, the PET and PBT contained in the single-layer film can have a concentration gradient along the thickness direction. To obtain such a single-layer film, it is preferable that PET and PBT are predominantly present in the resin composition used to form the single-layer film using known methods. Specifically, the conditions during the manufacturing of the single-layer film can also be appropriately adjusted. For example, the temperature during the melt mixing and extrusion of the resin composition into a film can be set low, or the screw speed can be appropriately adjusted to reduce the degree of mixing, thereby preventing excessive promotion of the reaction between PET and PBT, and adjusting the concentration gradient using the difference in their surface free energies. Furthermore, in this manufacturing method, the particles themselves can also have a concentration gradient.

[0297] The unstretched sheet obtained as described above is stretched in both the longitudinal and transverse directions. There are no particular limitations on the stretching method; it is preferable to use a roller-type or tenter-type stretching machine. Furthermore, stretching is preferably performed in the transverse direction after the longitudinal direction, but the reverse is also possible.

[0298] Here, the stretching temperature during longitudinal stretching is preferably 50°C or higher and 85°C or lower, more preferably 58°C or higher and 75°C or lower, even more preferably 60°C or higher and 75°C or lower, and even more preferably 65°C or higher and 75°C or lower. The longitudinal stretching ratio is preferably 2.5 times or higher and 4.5 times or lower, more preferably 2.8 times or higher and 4.2 times or lower, even more preferably 3 times or higher and 4 times or lower, and even more preferably 3.2 times or higher and 3.8 times or lower.

[0299] Furthermore, during transverse stretching, it is preferable to preheat the polyester film before stretching. The preheating temperature is preferably 60°C or higher and 90°C or lower, more preferably 64°C or higher and 90°C or lower, even more preferably 65°C or higher and 85°C or lower, and even more preferably 70°C or higher and 85°C or lower. Additionally, the stretching temperature during transverse stretching is, for example, 70°C or higher and 120°C or lower, preferably 75°C or higher and 120°C or lower, more preferably 75°C or higher and 110°C or lower, even more preferably 77°C or higher and 100°C or lower, and even more preferably 80°C or higher and 95°C or lower. Furthermore, the transverse stretching ratio is preferably 3.5 times or higher and 6 times or lower, more preferably 4 times or higher and 5.6 times or lower, and even more preferably 4.2 times or higher and 5.2 times or lower.

[0300] Regarding the transverse stretch ratio mentioned above, it is a relatively low ratio even though PBT is used. This polyester film is usually manufactured as a raw material film with a length (film width) of a certain size in the TD direction, but as mentioned above, by suppressing the transverse stretch ratio to a low level, various physical properties can be kept within the desired range, and the unevenness of various physical properties (such as orientation, puncture strength, displacement during puncture, etc.) of the raw material film near the center and ends in the TD direction can be suppressed.

[0301] Furthermore, after the polyester film is stretched in the longitudinal and transverse directions as described above, it is preferable to then perform a heat setting treatment at a heat setting temperature of 180°C or higher to obtain a biaxially stretched polyester film. The heat setting treatment is preferably performed at the aforementioned heat setting temperature under applied tension or with a relaxation of 30% or less, preferably 10% or less, and more preferably 7% or less.

[0302] In this manufacturing method, the ratio of transverse stretch ratio to longitudinal stretch ratio (TD / MD) is preferably 1 or more and 1.7 or less. By setting the ratio of transverse stretch ratio to longitudinal stretch ratio within a certain range, and by setting the stretching temperature during transverse stretching within a certain range after preheating as described above, and by setting the heat setting temperature after stretching to a certain temperature or above, it is easy to adjust the heat shrinkage rate to a specified range. The ratio of transverse stretch ratio to longitudinal stretch ratio (TD / MD) is more preferably 1.1 or more and 1.7 or less, and even more preferably 1.2 or more and 1.7 or less. Furthermore, the ratio of transverse stretch ratio to longitudinal stretch ratio (TD / MD) is also more preferably 1.1 or more and 1.6 or less, and even more preferably 1.2 or more and 1.5 or less.

[0303] Furthermore, in this manufacturing method, as described above, by keeping the stretching temperature during longitudinal stretching, as well as the transverse stretching ratio and longitudinal stretching ratio within a certain range, it is even easier to adjust the heat shrinkage rate to the desired range.

[0304] Furthermore, from the viewpoint of minimizing heat shrinkage, a high heat-setting temperature is preferred, preferably 190°C or higher, more preferably greater than 190°C, even more preferably 195°C or higher, and even more preferably 200°C or higher. The heat-setting temperature is not particularly limited, but preferably 240°C or lower, more preferably 230°C or lower, even more preferably 225°C or lower, and even more preferably 220°C or lower. The heat-setting time is preferably 3 seconds or more and 15 seconds or less, more preferably 4 seconds or more and 14 seconds or less, and even more preferably 5 seconds or more and 13 seconds or less.

[0305] Furthermore, in this manufacturing method, as described above, by setting the ratio of transverse stretching ratio to longitudinal stretching ratio to a certain range, setting the stretching temperature during transverse stretching to a certain range after preheating, and setting the heat setting temperature after stretching to a certain temperature or above, it is possible to improve the overall orientation degree (surface orientation degree) of the polyester film, and control the difference between transverse orientation degree (Δnv) and longitudinal orientation degree (Δnp) to a certain level or below.

[0306] It should be noted that, after the heat setting process, a cooling treatment can also be performed in a cooling zone at a relaxation level of, for example, 0-20%, preferably 0.5-15%, more preferably 1-10%, and even more preferably 1.5-7%. The cooling temperature is preferably around 120-160°C, and more preferably around 130-150°C.

[0307] Furthermore, in this manufacturing method, the product of the transverse stretching ratio and the longitudinal stretching ratio is preferably 14 or more, more preferably 15 or more, and even more preferably greater than 15.5; it is also preferably 25 or less, more preferably 20 or less, and even more preferably 18 or less.

[0308] Furthermore, in this manufacturing method, the difference between the transverse stretching ratio and the longitudinal stretching ratio is preferably 0.3 times or more, more preferably 0.5 times or more, and even more preferably 0.7 times or more; in addition, it is, for example, 2.4 times or less, preferably 2 times or less, more preferably 1.8 times or less, and even more preferably 1.6 times or less.

[0309] By adjusting the transverse stretch ratio and longitudinal stretch ratio within a certain range as described above, this polyester film can achieve good physical properties and suppress the unevenness of various physical properties (such as orientation, puncture strength, displacement during puncture, etc.) of the raw material film in the central and end areas in the TD direction.

[0310] The stretch ratio, for example, in the longitudinal direction, is determined by the ratio of the membrane conveying speed before stretching to the membrane conveying speed after stretching. In the transverse direction, it is determined by the ratio of the membrane width before stretching to the length of the membrane width after stretching.

[0311] It should be noted that when the polyester film has functional layers such as functional layer X and easy-to-adhere layer, the method for forming these functional layers is not particularly limited. Examples include online coating and offline coating. From the viewpoint of adapting to thin film production and reducing the number of manufacturing steps, online coating is preferred. Online coating is a method of coating within the polyester film manufacturing process. More specifically, it is preferable to coat the film after the polyester melt extrusion, after longitudinal stretching, and before transverse stretching. Offline coating refers to a method of setting the easy-to-adhere layer using a coating apparatus in another process after the polyester film has been formed.

[0312] <Layered Body>

[0313] This polyester film is used, for example, in laminates. This polyester film is preferably used as a battery outer packaging material after being laminated. The laminate of the present invention includes this polyester film. In addition to the aforementioned polyester film, the laminate of the present invention preferably includes at least one of a resin layer, a metal layer, and a sealing layer, and more preferably includes at least one of a resin layer and a metal layer.

[0314] The metal layer is a layer formed from metal, metal oxide, or a mixture of metal and metal oxide. Preferably, the metal layer is formed from a metal, such as aluminum, nickel, titanium or their alloys, stainless steel, titanium steel, etc., with aluminum alloys being more preferred. The metal layer can be formed from metal foil or by metal vapor deposition, but metal foil is preferred. From the viewpoint of preventing wrinkles and pinholes, the metal layer is more preferably formed from, for example, annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O) or other soft aluminum alloy foil.

[0315] The metal layer can be a single layer or a laminate of two or more layers. The thickness of the metal layer is not particularly limited as long as it functions as a barrier against water vapor, but from the viewpoint of reducing the thickness of the flexible package, it is preferably about 100 μm or less, more preferably 3 μm or more and 100 μm or less, even more preferably 3 μm or more and 80 μm or less, even more preferably 6 μm or more and 60 μm or less, and even more preferably 10 μm or more and 40 μm or less.

[0316] Furthermore, from the viewpoints of stabilizing the adhesion and preventing dissolution and corrosion, it is preferable that at least one side, and more preferably both sides, of the metal layer has undergone chemical conversion treatment. Here, chemical conversion treatment is a process of forming an acid-resistant film on the surface of the metal layer. The metal layer may have an acid-resistant film on one side, on both sides, or without an acid-resistant film.

[0317] There are no particular limitations on the thickness of the acid-resistant coating. However, from the viewpoint of the coating's cohesiveness and adhesion to the metal layer and the heat-fused resin layer, it is preferably 1 nm or more and 1000 nm or less, more preferably 3 nm or more and 100 nm or less, and even more preferably 5 nm or more and 50 nm or less. It should be noted that the thickness of the acid-resistant coating can be determined by transmission electron microscopy, or by a combination of transmission electron microscopy and energy-dispersive X-ray spectroscopy or electron beam energy loss spectroscopy.

[0318] The chemical conversion treatment is preferably carried out by applying a solution containing a compound for forming an acid-resistant film onto the surface of a metal layer using methods such as bar coating, roller coating, gravure coating, or immersion coating, followed by heating to a temperature of, for example, 70°C or higher but below 200°C. Prior to the chemical conversion treatment, the metal layer can be pre-treated with degreasing methods such as alkaline immersion, electrolytic cleaning, pickling, or electrolytic pickling.

[0319] Examples of resins constituting the resin layer include polyester resin, polyamide resin, polyolefin resin, epoxy resin, acrylic resin, fluororesin, polyurethane resin, silicone resin, and phenolic resin, as well as mixtures of these resins. Polyester resin and polyamide resin are preferred, with polyamide resin being the most preferred.

[0320] As for polyamide resins, there are no particular limitations, but examples include: aliphatic polyamides such as polyamide 6, polyamide 66, polyamide 510, polyamide 12, polyamide 46, and copolymers of polyamide 6 and polyamide 66; aromatic polyamides such as polyamide 6I, polyamide 6T, polyamide 6IT, and polyamide 6I6T (where I represents isophthalic acid and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid; alicyclic polyamides such as poly(methylenediamine)-isophthalic acid-terephthalic acid copolymers; poly(methylenediamine)-adipamide (MXD6); alicyclic polyamides such as polyaminomethylcyclohexylhexamethylenediamide (PACM6); polyamides further copolymerized with lactam components and isocyanate components such as 4,4'-diphenylmethane-diisocyanate; copolymers of copolyamides with polyesters and polyalkylene ether diols, i.e., polyesteramide copolymers; polyether esteramide copolymers; and these copolymers. They can be used individually, or in combination of two or more.

[0321] Furthermore, a resin film is preferred as the resin layer, and a stretched film is preferred from the viewpoint of mechanical strength. The stretched film can be a uniaxial stretched film or a biaxial stretched film. Therefore, the resin layer is preferably composed of a polyamide film, and more preferably a stretched polyamide film. The stretched polyamide film can be manufactured by conventionally known methods. For example, as stretching methods for forming a biaxial stretched polyamide film, examples include sequential biaxial stretching, blow-up, and simultaneous biaxial stretching, with sequential biaxial stretching being preferred.

[0322] The resin layer can be a single layer or a laminate of two or more layers. The thickness of the resin layer is, for example, 5 μm or more and 80 μm or less, preferably 8 μm or more and 60 μm or less, and more preferably 10 μm or more and 40 μm or less.

[0323] The thickness ratio of the polyester film to the metal layer (polyester film layer: metal layer) is preferably in the range of 1:1 to 1:5, more preferably in the range of 1:1.1 to 1:4, and even more preferably in the range of 1:1.2 to 1:3.

[0324] Furthermore, the laminate can include a sealing layer. By having a sealing layer, the laminate can be thermally fused to a sealing layer disposed on other components, thereby adhering it to those other components. Therefore, by having a sealing layer, the laminate can be easily formed into an outer packaging material through lamination or similar processes. It should be noted that while the laminates of the present invention can be bonded to each other via sealing layers, the laminates of the present invention can also be bonded to components other than the laminates of the present invention via sealing layers.

[0325] The sealing layer can be formed of a heat-weldable resin material. Examples of resins constituting the sealing layer include polyolefins, cyclic polyolefins, carboxylic acid-modified polyolefins, and carboxylic acid-modified cyclic polyolefins, with carboxylic acid-modified polyolefins being preferred and carboxylic acid-modified polypropylene being more preferred.

[0326] As polyolefins, examples include: low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, and other polyethylenes; homopolymer polypropylene, polypropylene block copolymers (e.g., block copolymers of propylene and ethylene), polypropylene random copolymers (e.g., random copolymers of propylene and ethylene), and ethylene-butene-propylene terpolymers. Among these, polyethylene and polypropylene are preferred, and polypropylene is more preferred.

[0327] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. Examples of olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Furthermore, examples of cyclic monomers constituting the cyclic polyolefin include norbornene and other cyclic olefins; specifically, examples include cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene. Among these, cyclic olefins are preferred, and norbornene is more preferred. Additionally, styrene may also be used as a constitutive monomer.

[0328] The carboxylic acid-modified polyolefin refers to a polymer modified by block polymerization or graft polymerization of the polyolefin with a carboxylic acid. Examples of carboxylic acids used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0329] The sealing layer is, for example, 10 μm or more and 100 μm or less, preferably 15 μm or more and 80 μm or less, and about 20 μm or more and 60 μm or less.

[0330] An adhesive layer may be present between the layers (e.g., between the resin layer and the polyester film, between the resin layer and the metal layer, between the polyester film and the metal layer, etc.), and the layers are bonded together via the adhesive layer. There are no particular limitations on the adhesive layer; it is preferable to use a known adhesive, such as a polyether-based adhesive, a polyester-based adhesive, a polyurethane-based adhesive, an epoxy-based adhesive, a phenolic resin-based adhesive, a polyamide-based adhesive, a polyolefin-based adhesive, a polyacrylic acid-based adhesive, an amino resin-based adhesive, a rubber-based adhesive, or a silicone-based adhesive. Furthermore, there are no particular limitations on the bonding between the layers; it is preferable to use a known lamination method such as dry lamination.

[0331] The laminate of the present invention preferably has at least a metal layer. By having a metal layer, the laminate can improve its strength and function as a barrier layer to prevent the transmission of water, steam, oxygen, light, etc., making the laminate suitable as a battery outer packaging material.

[0332] When the laminate has a metal layer, the metal layer can be present on one side of the polyester film. Alternatively, the metal layer can be bonded to the polyester film via an adhesive layer.

[0333] When the laminate of the present invention has a metal layer, a resin layer may be further provided between the metal layer and the polyester film. In this case, an adhesive layer is preferably further provided between the polyester film and the resin layer, and between the resin layer and the metal layer, for bonding.

[0334] This polyester film is preferably disposed as the outermost layer in a laminate. In particular, this polyester film is preferably the outermost layer for battery packaging materials. The outermost layer of a laminate is easily damaged by external forces during molding and use, but this polyester film, as described above, provides good puncture resistance, and also improves martensitic hardness, indentation hardness, etc., resulting in excellent resistance to pinholes and tensile strength. Therefore, by using this polyester film as the outermost layer of the laminate, it is easy to appropriately prevent damage to the laminate during molding and damage to the battery packaging material containing the laminate. Furthermore, from the same viewpoint, when this polyester film has a surface with a content (A1) higher than a content (A2), it is preferable that the surface with a content (A1) higher than a content (A2) is disposed as the outermost layer of the laminate.

[0335] Furthermore, when the polyester film has a functional layer X, the functional layer X is preferably disposed at the position in contact with the mold as described above. Therefore, the functional layer X is preferably disposed on the outermost side of the laminate. That is, it is also preferable that the surface of the polyester film having the functional layer X, and having a content (A1) higher than a content (A2), is disposed on the outermost side of the laminate.

[0336] Preferred laminated structures for the laminated body of the present invention include: the polyester film / adhesive layer / metal layer, the polyester film / adhesive layer / resin layer / adhesive layer / metal layer, and other laminated structures.

[0337] Furthermore, the laminate of the present invention preferably has a laminate structure that includes a sealing layer in addition to the metal layer. Examples of preferred laminate structures that include both a metal layer and a sealing layer include: a polyester film / adhesive layer / metal layer / sealing layer, and a polyester film / adhesive layer / resin layer / adhesive layer / metal layer / sealing layer, etc.

[0338] It should be noted that the sealing layer can be directly bonded to the metal layer or bonded via an adhesive layer. Furthermore, the resin constituting the resin layer is preferably a polyamide resin. Therefore, the resin layer in each of the above-described laminated structures is preferably a polyamide resin layer, and more preferably a stretched polyamide film.

[0339] <Application>

[0340] This polyester film is preferably used in molded articles. This polyester film can be used as a battery outer packaging material for various batteries, including lithium-ion batteries, lithium-ion polymer batteries, lead-acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver-zinc oxide batteries, metal-air batteries, and multivalent cation batteries, to package battery components such as battery cells, represented by energy storage devices. That is, the present invention also provides a battery outer packaging material having the aforementioned polyester film or laminate, and a battery having the battery outer packaging material. For example, in the aforementioned laminate, this polyester film prevents a decrease in adhesion to other components such as metal foil, and is easily laminated onto other films during lamination, thus making it suitable for battery outer packaging. Furthermore, this polyester film is expected to possess chemical resistance, and considering factors such as improved puncture resistance, it is suitable for use as a battery outer packaging. Of the above, this polyester film is particularly suitable for lithium battery outer packaging, especially for automotive lithium battery outer packaging.

[0341] This polyester film is preferably shaped and used as a battery outer packaging material. It is generally preferred that this polyester film be shaped and formed in the state described above as a laminate, but it can also be shaped and formed as a single layer. By shaping this polyester film, for example by forming recesses, components constituting a battery, such as energy storage devices, can be accommodated inside the recesses.

[0342] Shaping is a method of shaping a polyester film or laminate into a desired shape using a mold. Shaping is not particularly limited and can be performed using any forming method such as vacuum forming, pneumatic forming, or stamping. Furthermore, cold forming is preferred. Moreover, deep drawing is preferred. The polyester film of the present invention exhibits good elongation, allowing for proper shaping without damage even when formed using shaping, particularly deep drawing.

[0343] The battery outer packaging material can have any composition as long as it contains this polyester film or the aforementioned laminate, but it is preferable that the outer packaging material has the aforementioned laminate, and more preferably any of the aforementioned laminate structures. In the battery outer packaging material, it is preferable that the polyester film is disposed on the outer side, preferably the outermost layer, and the metal layer is disposed on the inner side of the laminate having the aforementioned laminate structure. That is, when this polyester film is used in the battery outer packaging material, it is preferable to use it as the outermost layer of the battery outer packaging material. This polyester film can improve chemical resistance, so by being disposed on the outer side of the outer packaging material (preferably the outermost layer), the internal components of the outer packaging material can be adequately protected. In addition, it can also appropriately prevent delamination and other issues caused by electrolyte leakage.

[0344] Furthermore, the battery outer packaging material of the present invention is preferably as follows: components constituting a battery, such as battery cells, are held together, for example, by a pair of laminated bodies, and the peripheries of the laminated bodies are heat-fused together via a sealing layer through lamination or the like, thereby sealing the battery cells and other components inside. Furthermore, the battery outer packaging material of the present invention is preferably as follows: a recess is formed by shaping, and components such as battery cells are accommodated in this recess; after the laminated bodies having the recesses are heat-fused together via a sealing layer, the battery cells and other components are sealed inside.

[0345] <<Explanation of the statement>>

[0346] In this invention, even when referred to as a "membrane", it also includes a "sheet", and even when referred to as a "sheet", it also includes a "membrane".

[0347] In this invention, when referred to as "X to Y" (where X and Y are arbitrary numbers), unless otherwise stated, it not only means "more than X and less than Y", but also includes the meaning of "preferably greater than X" or "preferably less than Y".

[0348] Furthermore, when it is stated as "X or more" (where X is any number), unless otherwise stated, it includes the meaning of "preferably greater than X"; when it is stated as "Y or less" (where Y is any number), unless otherwise stated, it includes the meaning of "preferably less than Y".

[0349] Example

[0350] The present invention will be further described in detail below through embodiments. However, the present invention is not limited to the following embodiments as long as it does not depart from its spirit.

[0351] <Evaluation Methods>

[0352] (1) Determination of intrinsic viscosity (dl / g) of polyester and film

[0353] Accurately weigh 1g of polyester and dissolve it in 100ml of a phenol / tetrachloroethane mixture (50 / 50 mass ratio). Measure the intrinsic viscosity at 30°C. Note that if particles are present, accurately weigh 1g of polyester after removing the particles and then measure the intrinsic viscosity.

[0354] (2) Lateral orientation (Δnv), longitudinal orientation (Δnp), and planar orientation (ΔP)

[0355] The transverse orientation (Δnv), longitudinal orientation (Δnp), and planar orientation (ΔP) were measured according to the method described in the instruction manual.

[0356] (3-1) Puncture strength (N / mm) and displacement (mm) during puncture strength measurement

[0357] Puncture strength (N) was determined according to JIS Z1707:2019. The puncture strength (N / mm) was obtained by dividing the measured puncture strength (N) by the film thickness. Furthermore, the displacement during puncture strength measurement was taken as the displacement during puncture. The average value of 12 points was used for the measurement. Specifically, a 210mm × 297mm sample was cut from the center of the film roll obtained by the method described below, with the short side as the transverse direction of the film. Twelve points were randomly selected evenly from the cut sample for measurement, and the average value of these measurements was used.

[0358] (3-2) Uneven puncture intensity and uneven displacement during puncture

[0359] Using the measured values ​​of puncture intensity and displacement at the 12 points obtained above as coefficients of variation, the non-uniformity of puncture intensity and displacement during puncture are evaluated by the following formula (1). It can be said that the smaller the value, the smaller the non-uniformity.

[0360] Equation (1) = Standard deviation / Mean

[0361] (4) Glass transition temperature (Tg), number of endothermic peaks, and melting point (Tm)

[0362] Using a differential scanning calorimeter (PerkinElmer Japan, Diamond DSC), the temperature was increased from -70°C to 280°C at a rate of 10°C / min, held for 10 minutes, and then decreased to -70°C at a rate of 600°C / min. The temperature was then increased again at a rate of 10°C / min. The change in specific heat caused by the transition from the glassy to the rubbery state during the second heating process was recorded, and the glass transition temperature (Tg) was calculated. It should be noted that the midpoint glass transition temperature was used as Tg. Furthermore, when heating and cooling were performed similarly using the differential scanning calorimeter, the peak temperatures of each endothermic peak observed in the first heating process (first heating scan) and the second heating process (second heating scan) were taken as melting points, and their values ​​are shown in Table 2. When more than two peaks were observed, all values ​​were recorded. Therefore, one value in the melting point column indicates one endothermic peak, and two values ​​in the melting point column indicate two endothermic peaks. It should be noted that when more than two endothermic peaks are observed, the temperature at the peak of the largest peak is taken as the melting point.

[0363] (5) Thermal shrinkage rate

[0364] Samples of polyester films with dimensions of 15 mm × 150 mm obtained in the examples and comparative examples were heated in an oven at 160°C for 15 minutes under no-tension conditions. The length of the samples before and after heating was measured, and the heat shrinkage rates of the longitudinal (MD) and transverse (TD) sections of the film were calculated using the following formula.

[0365] Heat shrinkage rate (%) = {(L0-L1) / L0} × 100

[0366] (In the formula, L0 is the sample length before heat treatment, and L1 is the sample length after heat treatment.)

[0367] It should be noted that five points were measured on both the longitudinal (MD) and transverse (TD) sides of the membrane, and the average value was calculated for each.

[0368] (6) Haze

[0369] The haze was measured using a NDH-2000 haze meter manufactured by Nippon Denshoku Kogyo Co., Ltd., in accordance with JIS K7136:2000.

[0370] (7) Martens hardness, indentation hardness and elastic deformation power

[0371] Approximately 2–8 mg of Aron Alpha (registered trademark) (General Chemical, Toa Synthetic Chemical Co., Ltd.) was dropped onto a glass slide (S1112, manufactured by Matsunami Glass Industry Co., Ltd.). A polyester film (1.5 cm × 1.5 cm) was then placed on the slide as an adhesive surface, covering one side (the side opposite to the test surface) and allowed to cure. The slide with the polyester film was fixed onto the stage of a hardness tester (Dynamic Microhardness Tester (DUH-211S, manufactured by Shimadzu Corporation)). A load-unload test was then performed on the surface of the polyester film, and the elastic deformation power (η) was calculated using the following formula. it It also measures martensitic hardness and indentation hardness. It should be noted that each value is calculated as the average of 10 measurements taken with n=11, excluding the initial point.

[0372] Wtotal=Wplast+Welast(N·m)

[0373] (Wtotal = total deformation work (N·m), Wplast = plastic deformation work (N·m), Welast = elastic deformation work (N·m))

[0374] η it =(Welast / Wtotal)×100(%)

[0375] (Measurement conditions)

[0376] Indenter used: Diamond equilateral triangular pyramid indenter (angle between edges: 115°).

[0377] Measurement mode: Load-unload test.

[0378] Test force: 20.00mN.

[0379] Minimum test force: 0.20mN.

[0380] Load speed: 0.1464 mN / sec.

[0381] Load retention time: 2 seconds.

[0382] Uninstallation retention time: 0 seconds.

[0383] Measurement atmosphere: 23±2℃, relative humidity 50±5%.

[0384] The number of n was determined to be 11.

[0385] <Materials Used>

[0386] [Polyester raw materials]

[0387] (PBT)

[0388] PBT-A: Butylene terephthalate (intrinsic viscosity = 0.85 dL / g).

[0389] PBT-B: Butylene terephthalate (intrinsic viscosity = 1.26 dL / g).

[0390] (PET)

[0391] PET-A: Homopolymer polyethylene terephthalate (intrinsic viscosity = 0.64 dL / g).

[0392] PET-B: Homopolymer polyethylene terephthalate (intrinsic viscosity = 0.85 dL / g).

[0393] PET-C: A masterbatch made by adding 0.55% by mass of silica particles with an average particle size of 3.1 μm to homopolymer polyethylene terephthalate (intrinsic viscosity = 0.61 dl / g).

[0394] PET-D: A masterbatch (intrinsic viscosity = 0.60 dl / g) made by mixing 10% by mass of organic particles (spherical particles polymerized from acrylate monomers, styrene monomers, and organosilicon monomers) with an average particle size of 4.1 μm into homopolymer polyethylene terephthalate.

[0395] PET-E: Homopolymer polyethylene terephthalate (intrinsic viscosity = 0.60 dL / g).

[0396] PET-F: A masterbatch made by adding 0.60% by mass of silica particles with an average particle size of 3.2 μm to homopolymer polyethylene terephthalate (intrinsic viscosity = 0.62 dl / g).

[0397] (Example 1)

[0398] As shown in Table 2, PBT-A, PET-A and PET-C were dry-mixed at a mass ratio of 20:70:10 as the raw materials for the surface layer; PBT-A and PET-A were dry-mixed at a mass ratio of 20:80 as the raw materials for the core layer.

[0399] The mixed raw materials for the surface layer and the core layer were fed into different twin-screw extruders, mixed at 280°C, co-extruded at 280°C, and then cooled and solidified on cooling rollers set at 25°C using an electrostatic application method to obtain two types of three-layer (surface layer / core layer / surface layer) unstretched films.

[0400] Next, the obtained unstretched film was stretched to 3.5 times its original length in the longitudinal (MD) direction at 73°C using a roller stretching machine. Then, it was fed into a tenter frame stretching machine, preheated at 75°C for 6 seconds, and stretched to 4.5 times its original length in the transverse (TD) direction at 85°C. After stretching, it underwent a heat setting treatment at 210°C for 8 seconds, followed by a cooling treatment at 140°C with a 2% relaxation in the transverse (TD) direction, resulting in a biaxially stretched polyester film with a thickness of 25 μm (2.5 μm for each surface layer and 20 μm for the core layer). The obtained polyester film was evaluated. The evaluation results are shown in Table 2.

[0401] It should be noted that the PET / PBT mass ratio shown in Table 2 is the mass ratio of PET and PBT contained in the entire three-layer biaxially stretched polyester film. Specifically, the PET / PBT mass ratio of the entire polyester film is calculated from the blending ratio of PET and PBT in each layer and the thickness ratio of each layer, and the value is shown after rounding to one decimal place. In Comparative Example 1, the mass ratio of PET and PBT contained in the entire single-layer biaxially stretched polyester film is shown.

[0402] (Examples 2-6, 8-10, Comparative Examples 2-4)

[0403] Except for changing the composition of the surface and core layers and the membrane manufacturing conditions to those described in Table 2, the same procedure as in Example 1 was followed.

[0404] (Example 7)

[0405] The composition of the surface and core layers, as well as the film manufacturing conditions, were modified according to Table 2. The preheating time after longitudinal stretching was changed to 7 seconds, and the heat setting time was changed to 10 seconds. Furthermore, an easy-to-adhere coating liquid was applied to one side of the polyester film via online coating, after longitudinal stretching and before transverse stretching, at a coating amount (after drying and stretching) of 0.05 g / m². 2 The coating liquid is applied in the same manner to form an easy-to-adhere layer (functional layer), otherwise it is carried out in the same way as in Example 1.

[0406] (Formulation of coating liquid for easy-to-adhesive layers)

[0407] • 90% by mass of aqueous dispersion of polyester resin.

[0408] Monomer composition: (Acid component) Terephthalic acid / isophthalic acid / sodium 5-sulfoisophthalate = 56 / 40 / 4 (mol%), (Diol component) Ethylene glycol / 1,4-butanediol / diethylene glycol = 70 / 20 / 10 (mol%), a copolymerized polyester resin.

[0409] • Melamine compound: hexamethoxyhydroxymethyl melamine 9 by mass.

[0410] • Mass of silica particles with an average particle size of 0.07 μm.

[0411] (Examples 11 and 12)

[0412] The composition of the surface and core layers, as well as the film manufacturing conditions, were changed to those described in Table 2. The preheating time after longitudinal stretching was changed to 7 seconds, and the heat setting time was changed to 10 seconds. Otherwise, the process was the same as in Example 1. It should be noted that for Examples 4, 11, and 12, the martensitic hardness, indentation hardness, and elastic deformation power of the obtained polyester films were also measured, and the results are shown in Table 3.

[0413] (Comparative Example 1)

[0414] In Comparative Example 1, a single-layer polyester film was fabricated.

[0415] As shown in Table 2, PET-E and PET-F were dry-blended at a mass ratio of 92.5:7.5 as raw materials. The mixed raw materials were fed into a twin-screw extruder, compounded at 280°C, extruded at 280°C, and then cooled and solidified on a cooling roller set at 25°C using an electrostatic application method to obtain a single-layer unstretched film.

[0416] Next, the obtained unstretched film was stretched to 3.6 times its original length in the longitudinal direction (MD) at 89°C using a roller stretcher. Then, it was fed into a tenter frame, preheated at 112°C, and stretched to 4.4 times its original length in the transverse direction (TD) at 140°C. After stretching, it underwent a heat-setting treatment at 229°C for 8 seconds, followed by a cooling treatment at 140°C with a 7.3% relaxation in the transverse direction (TD), resulting in a single-layer polyester film with a thickness of 25 μm. The obtained polyester film was evaluated. The evaluation results are shown in Table 2.

[0417] [Table 2]

[0418]

[0419] [Table 3]

[0420]

[0421] The polyester film of the above embodiments contains both PBT and PET, and after heat treatment at 160°C for 15 minutes, the thermal shrinkage rate of the polyester film in one direction (longitudinal and transverse) is less than 5%, and the thermal shrinkage rate in the other direction is greater than 2.5%. Therefore, it is possible to provide a polyester film that prevents a decrease in adhesion to metal foil and is easy to laminate onto other films during lamination, making it suitable for use as battery outer packaging.

[0422] In contrast, the polyester film of Comparative Example 1, lacking PBT, exhibits a thermal shrinkage rate of less than 2.5% in both the longitudinal and transverse directions, resulting in reduced adhesion to the metal foil and rendering it unsuitable for use as battery packaging. Furthermore, the polyester films of Comparative Examples 2-4 have thermal shrinkage rates exceeding 5% in both the longitudinal and transverse directions, leading to high thermal shrinkage rates and making them difficult to laminate onto other films during lamination, thus also unsuitable for use as battery packaging.

[0423] It should be noted that the polyester films of Examples 11 and 12 contain both PBT and PET, and the PET content on the surface (A1) is higher than the PET content in the central portion in the thickness direction (A2). Therefore, compared to Example 4, which has the same PET content (A1) and (A2) on the surface and in the central portion in the thickness direction, the puncture strength, martensitic hardness, indentation hardness, and elastic deformation power are all higher. Therefore, it can be understood that the polyester films of Examples 11 and 12 have excellent pinhole resistance, are not easily damaged when subjected to external forces, and have excellent design flexibility and shape recovery, making them particularly suitable for battery packaging materials.

Claims

1. A polyester film comprising polybutylene terephthalate and polyethylene terephthalate, After heat treatment at 160°C for 15 minutes, the thermal shrinkage rate of the polyester film is less than 5% in one of the longitudinal and transverse directions, and greater than 2.5% in the other direction.

2. The polyester film according to claim 1, wherein, The endothermic peak obtained by differential scanning calorimetry during the temperature rise is one.

3. The polyester film according to claim 1, wherein, The ratio of the longitudinal heat shrinkage rate to the transverse heat shrinkage rate, MD / TD, is 0.7 or more and 2 or less.

4. The polyester film according to claim 1, wherein, The ratio of polyethylene terephthalate (PET) to polybutylene terephthalate (PBT) by mass is 55 / 45 or more and 95 / 5 or less.

5. The polyester film according to claim 1, wherein, The puncture strength is above 480 N / mm.

6. The polyester film according to claim 1, wherein, The displacement during puncture is more than 4 mm.

7. The polyester film according to claim 1, wherein, The puncture intensity was not uniformly below 0.

036.

8. The polyester film according to claim 1, wherein, The displacement during puncture was not greater than 0.

034.

9. The polyester film according to claim 1, wherein, The haze level is below 10%.

10. The polyester film according to claim 1, wherein, The melting point of the first temperature scan was above 230℃.

11. The polyester film according to claim 1, wherein, The intrinsic viscosity of the polyester film is above 0.6 dL / g and below 0.85 dL / g.

12. The polyester film according to claim 1, wherein, The polyester film is a biaxially stretched polyester film.

13. A method for manufacturing a polyester film, wherein the method for manufacturing the polyester film is the method for manufacturing a polyester film according to any one of claims 1 to 12. The method for manufacturing the polyester film includes steps of stretching in both the longitudinal and transverse directions. The preheating temperature for transverse stretching is above 60℃ and below 90℃, and the stretching temperature is above 70℃ and below 120℃.

14. The method for manufacturing a polyester film according to claim 13, wherein, The heat setting temperature after stretching is above 190°C.

15. The method for manufacturing a polyester film according to claim 13, wherein, The ratio of transverse stretch ratio to longitudinal stretch ratio, TD / MD, is greater than 1 and less than 1.

7.

16. The method for manufacturing a polyester film according to claim 13, wherein, The stretching temperature during longitudinal stretching is above 50℃ and below 85℃.

17. The method for manufacturing a polyester film according to claim 13, wherein, The longitudinal stretch ratio is more than 2.5 times and less than 4.5 times.

18. The method for manufacturing a polyester film according to claim 13, wherein, The lateral stretching ratio is 3.5 times or more and 6 times or less.

Citation Information

Patent Citations

  • Biaxially oriented polyester film for vessel molding, vessel and vessel molding process

    JP2004122767A

  • Biaxially stretched polyester film

    JP2006341546A

  • Polybutylene terephthalate film

    JP2012077292A

  • Polyester film, and laminate material containing the same, metal foil and sealant layer

    JP2017177412A

  • Polyester film

    JP2022056851A